Gas barrier laminate and method for producing same

By stacking a metal-containing layer and a gas barrier layer on a plastic substrate, a thinner gas barrier laminate is formed by using nano-indentation method and cooking treatment, which solves the problem of insufficient gas barrier performance in high temperature and high humidity environments, and achieves excellent gas barrier properties and fragrance retention.

CN119907741AActive Publication Date: 2025-04-29UNITIKA LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202480002760.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2024-09-26
Publication Date
2025-04-29
Estimated Expiration
2044-09-26

AI Technical Summary

Technical Problem

There is still room for improvement in the gas barrier performance of the existing gas barrier laminates in high temperature and high humidity environments, especially when locally bending, bent or elongated after vacuum packaging, the durability of the material and the barrier performance of the odor components are insufficient.

Method used

A gas barrier laminate containing a metal-containing layer and a gas barrier layer is used to form a thinner film by a specific manufacturing method, including laminating a gas barrier layer on a plastic substrate, and improving the composite elastic modulus and hardness of the gas barrier layer by using nano-indentation method and cooking treatment.

Benefits of technology

It achieves excellent gas barrier properties and fragrance retention in high temperature and high humidity environments, and can effectively block gas and odor components even if locally bent, bent or elongated after vacuum packaging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119907741A_ABST
    Figure CN119907741A_ABST
Patent Text Reader

Abstract

Provided is a gas barrier laminate which is a thinner film and which is capable of exhibiting excellent gas barrier properties and aroma retention properties in a high-temperature, high-humidity environment even after vacuum packaging. The present invention pertains to a gas barrier laminate characterized by comprising a plastic base material (I) and a gas barrier layer (II) laminated on the plastic base material, the gas barrier laminate having a total thickness of 100 [mu] m or less: (1) the plastic base material (I) comprising a metal-containing layer; the metal-containing layer contains a resin component and at least one of a metal and a metal compound, (2) the total content of the metal and the metal compound in the metal-containing layer is 0.1-20 mass%, (3) the gas barrier layer (II) contains a polycarboxylic acid, (4) the metal-containing layer and the gas barrier layer are laminated so as to be in direct contact with each other, and (5) the metal-containing layer and the gas barrier layer are laminated so as to be in direct contact with each other. And (5) the composite elastic modulus is 9.0-12.5 GPa when the surface of the gas barrier layer (II) is measured by a nanoindentation method when the laminate is subjected to a 120 DEG C retort treatment for 30 minutes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a gas barrier layered product and a method for producing the same. Background Art

[0002] Plastic films such as polyamide films are used in a wide range of applications as packaging materials due to their excellent strength, transparency, and formability. These plastic films have high permeability to oxygen and the like, so in the packaging of general foods, retorted foods, cosmetics, medical supplies, pesticides, etc., the contents may come into contact with the permeated oxygen and oxidize, resulting in discoloration or deterioration of taste.

[0003] Therefore, plastic films used for these packaging applications are required to have oxygen barrier properties, and packaging of foods containing water and the like also requires gas barrier properties under high humidity.

[0004] As a method for imparting oxygen barrier properties to a plastic film, a method of laminating a gas barrier layer on the film has been proposed. Specifically, as a gas barrier layer, it is known to use a gas barrier layer composed of a polycarboxylic acid polymer, a polyol polymer, and a metal compound. For example, Patent Document 1 etc. proposes a gas barrier laminate having excellent oxygen barrier properties in a high humidity environment close to room temperature.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2017-185652

[0008] Patent Document 2: Japanese Patent Application Publication No. 2007-276421

[0009] Patent Document 3: International Publication No. WO2014 / 042133

[0010] Patent Document 4: Japanese Patent Application Publication No. 2019-151025 Summary of the invention

[0011] Problems to be solved by the invention

[0012] However, although the gas barrier layered product disclosed in Patent Document 1 and the like has excellent gas barrier properties at around room temperature, there is still room for improvement in the gas barrier performance in a high temperature and high humidity environment.

[0013] In recent summers as global warming is trending, the surrounding environment during cargo transportation is extremely hot and humid. From the viewpoint of suppressing oxidative degradation of the contents, there is a strong demand for materials that can exhibit excellent gas barrier properties even in high temperature and high humidity environments. In particular, the gas barrier properties at high temperatures and high humidity above 40°C are receiving attention.

[0014] In particular, when the packaging material is used for vacuum packaging, further improvements are required, namely, gas barrier properties in a high temperature and high humidity environment in a state where local elongation, bending or folding occurs.

[0015] For example, Figure 3 As shown in FIG. 3A , when a vacuum packaged product is manufactured by sealing a food 31 (including processed products) with a packaging material 32, the packaging material 32 is disposed in a state of abutting against a portion of the surface of the food 31 before vacuuming. Figure 3 As shown in FIG. 3B, by performing vacuuming, the packaging material 32 is closely attached in a manner that follows the unevenness of the surface of the food 31. In this case, for example, Figure 3 In the region A of 3B, the packaging material follows the shape of the concave portion on the surface of the food, so that the packaging material is partially bent or folded. Figure 3 In region B of 3B, the packaging material follows the shape of the convex portion of the food surface, whereby the packaging material is partially stretched.

[0016] In this way, the packaging material is locally bent or folded along the shape of the surface of the content, or locally stretched, but the possibility of fine cracks being generated in these bent or folded parts or stretched parts, or fine cracks being generated over time, becomes high. From the above viewpoints, it is required to develop a packaging material that is also durable against local bending, bending and stretching.

[0017] Furthermore, packaging materials are required to prevent odor components (fragrance or odor) from leaking from the contents even in a high temperature and high humidity environment. In a high temperature and high humidity environment, the vapor pressure of odor components increases, and thus they are more likely to leak to the outside. Once the odor components of the contents leak, not only will the fragrance of the contents disappear or decrease, but the odor may also be transferred to other packaging materials, other products, etc. Therefore, packaging materials are also required to have the ability to block odor components (fragrance retention).

[0018] However, in order to improve the gas barrier properties, a method of increasing the thickness of the gas barrier film is generally considered, but from the viewpoints of the bag making properties of the film, the weight reduction of the film product, etc., and from the viewpoint of the volume reduction of raw materials in recent environmental issues, there is a demand for the development of thinner films.

[0019] Thus, there is a strong demand for the development of a material that can exhibit high gas barrier properties in a high-temperature and high-humidity environment despite being a thinner film (particularly a film with a total thickness of 100 μm or less), but such a material has not yet been developed.

[0020] Therefore, a main object of the present invention is to provide a gas barrier layered product which is a thinner film and can exhibit excellent gas barrier properties and fragrance retention properties even in a high-temperature and high-humidity environment after vacuum packaging.

[0021] Means for solving problems

[0022] The present inventors have conducted intensive studies in view of the problems of the prior art and, as a result, have found that a film obtained by a specific production method can achieve the above-mentioned object, thereby completing the present invention.

[0023] That is, the present invention relates to the following gas barrier layered product and a method for producing the same.

[0024] 1. A gas barrier layered product comprising a plastic substrate (I) and a gas barrier layer (II) laminated on the plastic substrate, wherein the total thickness of the gas barrier layered product is 100 μm or less.

[0025] (1) The plastic substrate (I) comprises a metal-containing layer, wherein the metal-containing layer comprises at least one of a metal and a metal compound and a resin component,

[0026] (2) The total content of the metal and the metal compound in the metal-containing layer is 0.1 to 20% by mass.

[0027] (3) the gas barrier layer (II) contains a polycarboxylic acid,

[0028] (4) the metal-containing layer and the gas barrier layer are stacked in direct contact with each other,

[0029] (5) The complex elastic modulus of the surface of the gas barrier layer (II) after the laminate was subjected to a retort treatment at 120° C. for 30 minutes, measured by a nanoindentation method, was 9.0 to 12.5 GPa.

[0030] 2. The gas barrier laminate according to item 1 above, wherein the hardness of the surface of the gas barrier layer (II) measured by nanoindentation after retorting the laminate at 120° C. for 30 minutes is 0.7 to 1.3 GPa.

[0031] 3. The gas barrier laminate according to item 1 or 2 above, wherein the laminate is subjected to a retort treatment at 120°C for 30 minutes, and is stretched by 7% in both the MD direction and the TD direction at a rate of 1.5% / s under a temperature of 35°C and a humidity of 50% RH, and the oxygen permeability of the laminate under a 40°C and 90% RH environment is 100 ml / (m 2 ·day·MPa) or less.

[0032] 4. The gas barrier layered product according to any one of items 1 to 3 above, wherein the plastic substrate (I) is composed of a multilayer film including a metal-containing layer.

[0033] 5. The gas barrier layered product according to any one of items 1 to 4 above, wherein the gas barrier layer (II) further contains a polyol.

[0034] 6. The gas barrier laminate according to any one of items 1 to 5, wherein the gas barrier layer (II) has a thickness of 0.05 to 5.00 μm, and the plastic substrate (I) has a thickness of 5 to 99.95 μm.

[0035] 7. The gas barrier layered product according to any one of items 1 to 6, wherein the polycarboxylic acid comprises at least one of polyacrylic acid, an acrylic acid-maleic acid copolymer, and an olefin-maleic acid copolymer.

[0036] 8. The gas barrier layered product according to any one of items 1 to 7 above, wherein the resin component contained in the metal-containing layer comprises one or more thermoplastic resins, and the content of the resin component in the metal-containing layer is 99.9 to 80% by mass.

[0037] 9. The gas barrier laminate according to any one of items 1 to 8 above, wherein the plastic substrate (I) is composed of one or more metal-containing layers and one or more other resin-containing layers, and the ratio of the total thickness (Mt) of the metal-containing layers (M) to the total thickness (Rt) of the other resin-containing layers (R) [(Rt) / (Mt)] is 1 / 10 to 10 / 1.

[0038] 10. The gas barrier multilayer according to any one of items 1 to 9 above, wherein the metal compound is at least one of lithium carbonate, sodium bicarbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium acetate, calcium oxide, calcium carbonate, calcium hydroxide, calcium chloride, calcium phosphate, calcium sulfate, calcium acetate, zinc acetate, zinc oxide and zinc carbonate.

[0039] 11. The gas barrier laminate according to any one of items 1 to 10, wherein the gas barrier layer (II) comprises an olefin-maleic acid copolymer, and the content of maleic acid units in the olefin-maleic acid copolymer is 5 mol % or more.

[0040] 12. The gas barrier layered product according to any one of items 1 to 11 above, wherein the metal and the metal compound are in a powdery form and have an average particle size of 0.005 to 5.0 μm.

[0041] 13. A packaging bag comprising the gas barrier laminate according to any one of Items 1 to 12.

[0042] 14. A vacuum-packaged product, wherein at least a solid component is contained and sealed in the packaging bag according to the above Item 13.

[0043] 15. A method for producing a gas barrier layered product, characterized in that it is a method for producing a gas barrier layered product, the method comprising:

[0044] (1) preparing a raw material solution, wherein the raw material solution comprises a polycarboxylic acid, a mineral oil and an acetylene glycol-based nonionic surfactant, wherein the mass ratio of the mineral oil to the acetylene glycol-based nonionic surfactant is 80 / 20 to 40 / 60; and

[0045] (2) A step of applying the raw material liquid as a coating liquid for forming a gas barrier layer (II) onto at least the surface of the metal-containing layer of a plastic substrate (I) comprising a metal-containing layer containing at least one of a metal and a metal compound and a resin component.

[0046] 16. The method according to item 15 above, further comprising the step of preparing a coating liquid for forming a gas barrier layer (II) by passing the raw material liquid through a filter having a filtration accuracy of 1.0 to 10.0 μm before applying the raw material liquid to the plastic substrate (I).

[0047] 17. The production method according to item 16 above, wherein the median particle size of the coating liquid for forming the gas barrier layer (II) after passing through the filter is 0.1 to 0.6 μm.

[0048] 18. The method for producing a gas barrier layered product according to any one of items 15 to 17, further comprising, after applying the raw material liquid to the plastic substrate (I), subjecting the layered product coated with the raw material liquid to simultaneous biaxial stretching or sequential biaxial stretching.

[0049] Effects of the Invention

[0050] According to the present invention, it is possible to provide a gas barrier layered product which is a thinner film and which can exhibit excellent gas barrier properties and fragrance retention properties even in a high-temperature and high-humidity environment after vacuum packaging.

[0051] In particular, in the present invention, by adopting a production method using a coating liquid containing a mineral oil and an acetylene glycol-based nonionic surfactant at a certain ratio (especially a coating liquid containing a pre-dispersion liquid in which the mineral oil is sufficiently dispersed), a specific gas barrier layer having a relatively uniform surface and a certain complex elastic modulus (hereinafter, also referred to as "elastic modulus") can be formed. Such a specific gas barrier layer can more reliably provide a gas barrier laminate that can exhibit excellent gas barrier properties and fragrance retention properties under harsh conditions such as high temperature and high humidity even after being stretched during vacuum packaging or bent or folded due to wrinkles.

[0052] Thus, the gas barrier laminate of the present invention is suitable for food applications that are not permeable to gases such as oxygen. In particular, even after elongation or bending or folding due to wrinkles or the like during vacuum packaging, it can still exhibit excellent gas barrier properties and aroma retention properties in a high temperature and high humidity environment. This can ensure a longer shelf life and shelf life, and further enable long-term and long-distance product transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0053] Figure 1 It is a figure which shows the layer constitution example of the gas barrier layered product of this invention.

[0054] Figure 2 This is a diagram showing another layer configuration example of the gas barrier layered product of the present invention.

[0055] Figure 3 This is a schematic diagram showing the state of the surface of the content and the packaging material when the content is sealed with the packaging material to produce a vacuum packaged product. DETAILED DESCRIPTION

[0056] 1. Gas barrier laminate

[0057] The gas barrier layered product of the present invention (the present invention layered product) is characterized by comprising a plastic substrate (I) and a gas barrier layer (II) laminated on the plastic substrate, wherein the total thickness of the gas barrier layered product is 100 μm or less.

[0058] (1) The plastic substrate (I) comprises a metal-containing layer, wherein the metal-containing layer comprises at least one of a metal and a metal compound and a resin component,

[0059] (2) The total content of the metal and the metal compound in the metal-containing layer is 0.1 to 20% by mass.

[0060] (3) the gas barrier layer (II) contains a polycarboxylic acid,

[0061] (4) the metal-containing layer and the gas barrier layer are stacked in direct contact with each other,

[0062] (5) The complex elastic modulus of the surface of the gas barrier layer (II) after the laminate was subjected to a retort treatment at 120° C. for 30 minutes, measured by a nanoindentation method, was 9.0 to 12.5 GPa.

[0063] exist Figure 1 An example of the layer constitution of the laminate of the present invention is shown in FIG. Figure 1 In the laminate 10 of 1A, the plastic substrate 11 is composed of a single layer of a metal-containing layer 11a containing a metal or a metal compound (hereinafter, unless otherwise specified, both are collectively referred to as "metal component"), and a gas barrier layer 12 is laminated on the surface of the metal-containing layer 11a. In this way, the metal component contained in the metal-containing layer 11a reacts with the polycarboxylic acid contained in the gas barrier layer 12 by the direct contact between the metal-containing layer 11a and the gas barrier layer 12, thereby being able to exhibit more excellent gas barrier properties. The reason why the gas barrier properties are enhanced by this reaction is considered to be that the metal component (metal ion) in the metal-containing layer (especially in the coating film of the coating liquid for forming the gas barrier layer described later) moves to the gas barrier layer, and in the gas barrier layer, the carboxyl group of the polycarboxylic acid reacts with the metal component, thereby forming a certain amount of cross-linking structure between the molecules of the polycarboxylic acid.

[0064] exist Figure 1 In the laminate 10' of 1B, the plastic substrate 11 is composed of a metal-containing layer 11a containing a resin component and a metal component and a resin-containing layer 11b and 11c that does not contain a metal component (hereinafter also referred to as "other resin-containing layer"), wherein a gas barrier layer 12 is laminated on the surface of the metal-containing layer 11a. In this case, the metal-containing layer 11a is in direct contact with the gas barrier layer 12, so that the metal component contained in the metal-containing layer 11a reacts with the polycarboxylic acid contained in the gas barrier layer 12, thereby achieving better gas barrier properties. The other resin layer is Figure 1 1B has 2 layers, but it only needs to have 1 layer or more.

[0065] exist Figure 1 In the laminate 10'' of 1C, the plastic substrate 11 is composed of a single layer of a metal-containing layer 11a containing a metal component, and gas barrier layers 12, 12 are respectively laminated on both surfaces of the metal-containing layer 11a. In this case, the metal-containing layer 11a is in direct contact with the gas barrier layers 12, 12, so that the metal component contained in the metal-containing layer 11a reacts with the polycarboxylic acid contained in the gas barrier layers 12, 12, thereby being able to exhibit better gas barrier properties.

[0066] exist Figure 1 1A Figure 1 In 1B, the metal-containing layer is only one layer, but two or more layers may be formed. Figure 2 As shown, the plastic substrate 11 is composed of a multilayer structure in which metal-containing layers 11a and 11a containing metal components are respectively laminated on both sides of the other resin-containing layer 11b, and it can also be a form in which gas barrier layers 12 and 12 are respectively laminated on the surface of each metal-containing layer 11a and 11a. That is, a layer structure in which two metal-containing layers 11a and 11a sandwich other resin-containing layers 11b is also included in the present invention. In this way, for the plastic substrate (I), a gas barrier layer (II) can be laminated on at least one side, and on the other hand, a gas barrier layer (II) or other barrier layers are also provided on the opposite side. In this way, by setting it as a double-sided coating formed by two metal-containing layers 11a and 11a, the gas barrier properties in a high temperature and high humidity environment can be further improved. It should be noted that a laminate having more than three metal-containing layers is also included in the present invention.

[0067] Hereinafter, each layer and the like constituting the gas barrier layered product of the present invention will be described in detail.

[0068] (1) About each layer

[0069] (1-1) Plastic substrate

[0070] The plastic substrate functions as a supporting member of the laminate of the present invention and also serves as a supply source for the metal component to the gas barrier layer.

[0071] The plastic substrate includes a metal-containing layer (a layer containing a metal element) containing at least one of a metal and a metal compound and a resin component. Therefore, the plastic substrate may be a multilayer including a metal-containing layer and other layers in addition to a single layer consisting of a single metal-containing layer. In addition, the metal-containing layer may have two or more layers.

[0072] As at least one of the metal and the metal compound, any one can be used as long as it can supply metal ions to the gas barrier layer to form the crosslinked structure as described above. More specifically, the following metals or metal compounds can be used.

[0073] The metal (metal element) is not limited, but from the viewpoint of gas barrier properties, monovalent metals such as lithium, sodium, potassium, rubidium, and cesium, and divalent or higher metals such as magnesium, calcium, zirconium, zinc, copper, cobalt, iron, nickel, and aluminum are preferred. Among them, metals with high ionization tendency are preferred from the viewpoint of easy reaction with carboxylic acid. Specifically, at least one of lithium, sodium, potassium, magnesium, calcium, and zinc is preferred, and at least one of magnesium, calcium, and zinc is more preferred.

[0074] The metal constituting the metal compound is not particularly limited, but from the viewpoint of gas barrier properties, preferred are monovalent metals such as lithium, sodium, potassium, rubidium, and cesium, and divalent or higher metals such as magnesium, calcium, zirconium, zinc, copper, cobalt, iron, nickel, and aluminum. The type of metal is not limited to one, and may be two or more. Among them, from the viewpoint of easy reaction with carboxylic acid, a metal with a high ionization tendency is preferred. Specifically, preferably, at least one of lithium, sodium, potassium, magnesium, calcium, and zinc, and particularly more preferably at least one of magnesium, calcium, and zinc.

[0075] The metal compound may be a compound containing the above metal, and examples thereof include inorganic salts such as oxides, hydroxides, halides, carbonates, bicarbonates, phosphates, and sulfates, carboxylates such as acetates, formates, stearates, citrates, malates, and maleates, and organic acid salts such as sulfonates. One or more of these may be used.

[0076] As specific examples of the metal compound, at least one of lithium carbonate, sodium bicarbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium acetate, calcium oxide, calcium carbonate, calcium hydroxide, calcium chloride, calcium phosphate, calcium sulfate, calcium acetate, zinc acetate, zinc oxide, zinc carbonate, etc. can be suitably used. In the present invention, at least one of oxides, hydroxides, carbonates, bicarbonates, acetates, etc. is preferred.

[0077] Particularly preferred from the viewpoint of gas barrier properties are magnesium salts such as magnesium oxide, magnesium carbonate, magnesium hydroxide, and magnesium acetate; calcium compounds such as calcium carbonate and calcium acetate; and divalent metal compounds such as zinc compounds such as zinc oxide and zinc acetate.

[0078] In addition, from the viewpoint of ensuring the transparency of the plastic substrate (I), monovalent metal compounds such as lithium carbonate and sodium bicarbonate, and divalent metal compounds such as magnesium oxide, magnesium carbonate, and magnesium hydroxide (particularly magnesium compounds) are preferred. One or more of these can be used. Among them, at least one of an oxide and a carbonate is particularly preferred.

[0079] In a preferred embodiment of the present invention, at least one of magnesium compounds can be suitably used as the metal component. More specifically, at least one of magnesium oxide, magnesium hydroxide, and magnesium carbonate can be suitably used.

[0080] The form of the metal component is not limited, and it is usually preferably in powder form. The average particle size at this time is not particularly limited, and it is usually in the range of about 0.001 to 10.0 μm, and is particularly preferably 0.005 to 5.0 μm, and further preferably 0.01 to 2.0 μm, among which 0.05 to 1.0 μm is most preferred. From the perspective of being able to improve the transparency of the plastic substrate (I), it is preferred that the average particle size of the metal component is small. On the other hand, metal components with an average particle size of less than 0.001 μm are easy to aggregate due to their large surface area, and coarse aggregates are scattered in the film, sometimes reducing the mechanical properties of the substrate. On the other hand, the plastic substrate (I) containing a metal component with an average particle size exceeding 10.0 μm has a tendency to increase the frequency of fracture during film formation and reduce productivity. In addition, if the average particle size exceeds 10.0 μm, it is sometimes not applicable when the thickness of the plastic substrate (I) is thin.

[0081] The particles of the metal component can be improved or enhanced in dispersibility, weather resistance, wettability with thermoplastic resin, heat resistance, transparency, etc. by performing surface treatment such as inorganic treatment and organic treatment. Examples of inorganic treatment include aluminum oxide treatment, silicon dioxide treatment, titanium dioxide treatment, zirconium oxide treatment, tin oxide treatment, antimony oxide treatment, zinc oxide treatment, etc. Examples of organic treatment include treatment using fatty acid compounds, polyol compounds such as pentaerythritol and trimethylolpropane, amine compounds such as triethanolamine and trimethylolamine, silicone resins, and silicone compounds such as alkylchlorosilanes.

[0082] The content of the metal component in the metal-containing layer (the total content of the metal element and the metal compound) is usually set to 0.1 to 20% by mass, particularly preferably 0.2 to 10% by mass, further preferably 0.3 to 5% by mass, and more preferably 0.3 to 3% by mass, and most preferably 0.3 to 1% by mass. If the content of the metal compound in the metal-containing layer is 0.1 to 20% by mass, the obtained gas barrier laminate can obtain excellent gas barrier properties and aroma retention properties. If the content of the metal compound is less than 0.1% by mass, the cross-linked structure formed by the reaction with the polycarboxylic acid of the gas barrier layer (II) is sometimes reduced, and the gas barrier properties of the obtained gas barrier laminate are reduced, or the hardness of the gas barrier layer (II) is lower than the preferred range, and the barrier properties after bending are reduced. On the other hand, the plastic substrate (I) having a content exceeding 20% ​​by mass has a higher frequency of breakage during stretching during film formation, and productivity is easily reduced. In addition, there is a tendency for the mechanical properties and transparency to decrease, and there is a case where the hardness of the gas barrier layer (II) exceeds the preferred range and the barrier properties after bending decrease.

[0083] The method of making the metal-containing layer contain a metal component is not particularly limited, and the metal component can be added at any time in the manufacturing process. For example, there can be mentioned: a) a method of adding a metal component when polymerizing a thermoplastic resin constituting the metal-containing layer; b) a method of kneading a thermoplastic resin and a metal component using an extruder; c) a method of preparing a masterbatch in which the metal component is kneaded to a high concentration and added to a thermoplastic resin for dilution (masterbatch method), etc. In the present invention, from the viewpoint of operating efficiency, the above-mentioned masterbatch method is preferably used.

[0084] In the present invention, the resin component constituting the metal-containing layer is not particularly limited, and usually one or two or more thermoplastic resins can be used.

[0085] As thermoplastic resins, for example, polyolefin resins such as polyethylene, polypropylene, and ionomers, polyamide resins such as nylon 6, nylon 66, nylon 46, nylon MXD6 (poly(m-xylene adipamide)), and nylon 9T, polyethylene terephthalate, polyethylene isophthalate, polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, polyester resins such as polylactic acid, vinyl chloride, polystyrene resins, polycarbonate resins, polyarylate resins, ethylene-vinyl acetate copolymers, and ethylene-vinyl alcohol copolymers can be cited. Among these thermoplastic resins, at least one of polyamide resins and polyester resins is preferred. In particular, when forming a packaging bag, polyamide resins (especially nylon 6) are more preferred from the perspective of excellent puncture strength, impact resistance, and the like. In addition, polyester resin (polyethylene terephthalate) is more preferred from the viewpoint of excellent heat resistance and economic efficiency. Therefore, these resin components can be appropriately selected according to the application of the laminate of the present invention.

[0086] It should be noted that the thermoplastic resin constituting the metal-containing layer may contain, in addition to components derived from biomass and chemically recycled resin components obtained by polymerizing recycled monomers or recycled oligomers obtained by depolymerizing resin waste materials, etc. as starting materials, any one or more of the following components, such as material recycled resin components obtained by pulverizing edge trimming scraps, cuttings, etc. generated during film manufacturing or by re-melting and granulating the above-mentioned scraps or defective films.

[0087] The content of the resin component in the metal-containing layer is usually set to the remainder excluding the metal component and additives added as needed. Therefore, for example, it can be set to 99.9 to 80 mass %, 99.8 to 100 mass %, 99.7 to 95 mass %, or 99.7 to 99 mass %.

[0088] The metal-containing layer may contain at least one of various additives such as a heat stabilizer, an antioxidant, a reinforcing material, a pigment, an anti-degradation agent, a weathering agent, a flame retardant, a plasticizer, a preservative, an ultraviolet absorber, an antistatic agent, an anti-blocking agent, etc., as required, within the range not hindering the effect of the present invention, within the range not adversely affecting the performance of the plastic substrate (I). In addition, for the purpose of improving the sliding property of the plastic substrate (I), an inorganic lubricant or an organic lubricant other than the metal component may be added to the metal-containing layer, and silica is particularly preferably added.

[0089] The total content of these additives is usually set to about 5% by mass or less in the metal-containing layer, but is not limited thereto. It should be noted that, when these additives also belong to the "at least one of the metal and the metal compound" of the metal-containing layer, the content of the additive is included in the content of the "at least one of the metal and the metal compound".

[0090] The thickness of the metal-containing layer (single layer) is not limited, but is usually within a range of about 5 to 100 μm, and particularly preferably 10 to 30 μm, from the viewpoint of thickness control and reactivity with the gas barrier layer.

[0091] As described above, the plastic substrate (I) may be composed of a single metal-containing layer or may be composed of a single or multiple metal-containing layer and another resin-containing layer.

[0092] As the other resin-containing layer at this time, any layer containing a thermoplastic resin may be used. As the thermoplastic resin, at least one of the above-mentioned thermoplastic resins that can be used in the metal-containing layer can be cited. In this case, the thermoplastic resin contained in the metal-containing layer and the thermoplastic resin contained in the other resin-containing layer may be the same as or different from each other.

[0093] In addition, in other resin-containing layers, at least one of the above-mentioned additives that can be used in metal-containing layers may be included within the range that does not hinder the effect of the present invention. In this case, the total content of the additives is usually set to about 5% by mass or less in other resin-containing layers (or each layer when the other resin-containing layer is more than one layer), but is not limited to this. Other resin-containing layers can be any of layers containing metal components or layers not containing metal components, and in particular, layers not containing metal components can also be appropriately used. In addition, the content of the resin component in other resin-containing layers is usually set to the remaining part except the above-mentioned additives. Therefore, for example, it can be set to about 95 to 100% by mass, but is not limited to this.

[0094] As described above, the plastic substrate (I) may be composed of a single metal-containing layer or a multilayered layer including other resin-containing layers. That is, the plastic substrate in the laminate of the present invention may be (a) composed of one or more metal-containing layers or (b) composed of one or more metal-containing layers and one or more other resin-containing layers.

[0095] In the case of (b) above, the thickness composition ratio of the metal-containing layer (M) and the other resin-containing layer (R) is not particularly limited. The ratio [(Rt) / (Mt)] of the total thickness (Mt) of the metal-containing layer (M) to the total thickness (Rt) of the other resin-containing layers (R) is preferably 1 / 1000 to 1000 / 1, more preferably 1 / 100 to 100 / 1, and most preferably 1 / 10 to 10 / 1 in terms of facilitating the thickness control of each layer.

[0096] The thickness of the plastic substrate (I) can be appropriately selected according to the mechanical strength required for the obtained gas barrier layered product. In particular, from the perspective of mechanical strength, ease of handling, etc., the thickness of the plastic substrate (I) can be generally set within a range of about 5 to 99.95 μm, particularly preferably 5 to 50 μm, further preferably 5 to 40 μm, and most preferably 10 to 30 μm.

[0097] (1-2) Gas barrier layer (II)

[0098] The gas barrier layer (II) constituting the laminate of the present invention contains a polycarboxylic acid. The polycarboxylic acid in the gas barrier layer (II) reacts with the metal component in the plastic substrate (I) (metal-containing layer) to exhibit gas barrier properties.

[0099] The polycarboxylic acid may be any compound (including polymers) having two or more carboxyl groups in the molecule. In addition, these carboxyl groups may form an acid anhydride structure.

[0100] As specific examples of polycarboxylic acids, 1,2,3,4-butanetetracarboxylic acid, polyacrylic acid, polymethacrylic acid, acrylic acid-methacrylic acid copolymer, acrylic acid-maleic acid copolymer, polymaleic acid, ethylene-maleic acid copolymer and other olefin-maleic acid copolymers, polysaccharides having carboxyl groups in side chains such as alginic acid, carboxyl-containing polyamides, carboxyl-containing polyesters, etc. can be illustrated. One or more of the polycarboxylic acids can be used.

[0101] When the polycarboxylic acid is a polymer, the weight average molecular weight is not limited, but is generally about 1,000 to 1,000,000, particularly preferably 10,000 to 150,000, and more preferably 15,000 to 110,000.

[0102] As shown in the production method described below, the polycarboxylic acid is preferably one in which 0.1 to 20 mol % (particularly 5 to 15 mol %) of the carboxyl groups of the polycarboxylic acid are neutralized with an alkali compound. This can provide better gas barrier properties.

[0103] In the present invention, among the above-mentioned polycarboxylic acids, at least one of polyacrylic acid, acrylic acid-maleic acid copolymer and olefin-maleic acid copolymer is preferably used. Among them, olefin-maleic acid copolymer is preferred. In particular, from the viewpoint of gas barrier properties, ethylene-maleic acid copolymer (hereinafter, sometimes abbreviated as "EMA") can be suitably used.

[0104] EMA can be obtained, for example, by polymerizing maleic anhydride and ethylene using a known method such as solution free radical polymerization. The maleic acid unit in the olefin-maleic acid copolymer easily becomes a maleic anhydride structure formed by dehydration cyclization of adjacent carboxyl groups in a dry state, and opens the ring to form a maleic acid structure when wet or in an aqueous solution. Therefore, in the present invention, unless otherwise specified, maleic acid units and maleic anhydride units are collectively referred to as "maleic acid units".

[0105] The content of the maleic acid unit in EMA is not limited, and is usually preferably 5 mol% or more, particularly preferably 20 mol% or more, further preferably 30 mol% or more, wherein, most preferably 35 mol% or more. The upper limit of the content of the above-mentioned maleic acid unit is not particularly limited, and is usually 90 mol% or less, and particularly preferably 80 mol% or less. In addition, the weight average molecular weight of EMA is not limited, and is usually preferably about 1,000 to 1,000,000, particularly more preferably 3,000 to 500,000, particularly more preferably 7,000 to 300,000, wherein, most preferably 10,000 to 200,000.

[0106] In the gas barrier layer (II), the polycarboxylic acid may be 100% by mass or less (for example, 50 to 80% by mass, and for example, 60 to 75% by mass), and other components may also be included. In the present invention, as other components, it is particularly preferred to contain a polyol. By containing a polyol, the polycarboxylic acid in the gas barrier layer (II) reacts with the polyol in addition to the metal component in the plastic substrate (I), thereby further improving the gas barrier properties. Therefore, in the gas barrier layer, the polyol may contain, for example, about 20 to 50% by mass, and preferably 25 to 40% by mass.

[0107] The polyol is not limited, and examples thereof include compounds having two or more hydroxyl groups in one molecule. These compounds may be any of low molecular weight compounds or high molecular weight compounds. In addition, these compounds may be used in one or more than one kind.

[0108] Examples of the low molecular weight compound include sugar alcohols such as glycerol and pentaerythritol, monosaccharides such as glucose, disaccharides such as maltose, and oligosaccharides such as galacto-oligosaccharide.

[0109] Examples of the polymer compound include polyvinyl alcohol (PVA), vinyl alcohol polymers such as ethylene-vinyl alcohol copolymers, and polysaccharides such as starch. The saponification degree of the polyvinyl alcohol, ethylene-vinyl alcohol copolymer, etc. is not limited, but is preferably 95 mol % or more, and more preferably 98 mol % or more. In addition, the average polymerization degree of the polyvinyl alcohol, ethylene-vinyl alcohol copolymer, etc. is not particularly limited, but is generally preferably about 50 to 2,000, and more preferably 200 to 1,000.

[0110] In the present invention, these polyols may be used alone or in combination of two or more. In the present invention, polyvinyl alcohol can be particularly preferably used.

[0111] The ratio of the polycarboxylic acid to the polyol in the gas barrier layer (II) is not limited as long as the desired effect can be obtained, but is usually preferably 0.01 to 20 in terms of the molar ratio of OH group to COOH group (OH group / COOH group), more preferably 0.01 to 10, particularly preferably 0.02 to 5, and most preferably 0.04 to 2.

[0112] In addition, the gas barrier layer (II) may contain at least one of polyacrylamide, polymethacrylamide and polyamine (these are also collectively referred to as "polyamines, etc."). By containing these compounds, the polycarboxylic acid in the gas barrier layer (II) reacts with these compounds in addition to the metal component in the plastic substrate (I), thereby further improving the gas barrier properties and aroma retention properties. Polyamines, etc. can use known or commercially available products.

[0113] In the present invention, polyamines are particularly preferably used. Polyamines having at least one type of amino group selected from primary amino groups and secondary amino groups as amino groups in the molecule can be used. Specific examples thereof include polyallylamine, polyvinylamine, branched polyethyleneimine, linear polyethyleneimine, polylysine, polysaccharides having amino groups in the side chains such as chitosan, and polyamides having amino groups in the side chains such as polyarginine. One or more of them can be used. In addition, the weight average molecular weight of the polyamine is not limited, but is generally preferably 5,000 to 150,000.

[0114] The mass ratio of the polyamine etc. to the polycarboxylic acid (polyamine etc. / polycarboxylic acid) in the gas barrier layer (II) is not particularly limited, but is usually preferably about 12.5 / 87.5 to 27.5 / 72.5 from the viewpoint of improving gas barrier properties.

[0115] The gas barrier layer (II) may contain a crosslinking agent. By containing a crosslinking agent, the gas barrier properties can be improved. The content of the crosslinking agent in the gas barrier layer (II) is preferably set to 0.1 to 30 parts by mass, and particularly preferably set to 1 to 20 parts by mass relative to 100 parts by mass of the polycarboxylic acid. As the crosslinking agent, a) a self-crosslinking compound, b) a compound having multiple functional groups that react with carboxyl groups in the molecule, etc. can be mentioned. In the case where the gas barrier layer (II) contains a polyol, it can be a compound having multiple functional groups that react with hydroxyl groups in the molecule. As a preferred crosslinking agent, for example, at least one of isocyanate compounds, melamine compounds, urea compounds, epoxy compounds, carbodiimide compounds, zirconium salt compounds such as ammonium zirconium carbonate, metal alkoxides, etc. can be mentioned.

[0116] Metal alkoxide refers to a compound containing a metal to which an alkoxy group is bonded. Examples of metal alkoxides include a) metal alkoxides to which a halogen is bonded in place of a part of the alkoxy group, and b) metal alkoxides to which an alkyl group substituted with a functional group reactive with a carboxyl group is bonded in place of a part of the alkoxy group.

[0117] Examples of the metal in the metal alkoxide include atoms such as Si, Al, Ti, and Zr. It should be noted that the metal in the present invention also includes semimetals such as Si.

[0118] Examples of the halogen include chlorine, iodine, and bromine. Examples of the functional group reactive with a carboxyl group include an epoxy group, an amino group, an isocyanate group, and a urea group. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, and an isobutyl group.

[0119] Specific examples of such metal alkoxides include at least one of alkoxysilane compounds such as tetramethoxysilane, tetraethoxysilane, chlorotriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-ureidopropyltriethoxysilane, and 3-isocyanatepropyltriethoxysilane; alkoxytitanium compounds such as titanium tetraisopropoxide and titanium tetraethoxide; alkoxyaluminum compounds such as triisopropoxyaluminum; and alkoxyzirconium compounds such as tetraisopropoxyzirconium.

[0120] These metal alkoxides may be used in the form of (a) a part or all of them hydrolyzed, (b) a part of them hydrolyzed and condensed, (c) a part of them completely hydrolyzed and partially condensed, or (d) a combination thereof.

[0121] When the metal alkoxide and the polycarboxylic acid are mixed, the two may react and become difficult to apply, so it is preferable to form a hydrolysis condensate in advance before mixing. As a method for forming the hydrolysis condensate, any method used in the known sol-gel method can be applied.

[0122] The gas barrier layer (II) may contain additives such as heat stabilizers, antioxidants, reinforcing materials, pigments, anti-degradation agents, weathering agents, flame retardants, plasticizers, mold release agents, lubricants, preservatives, wetting agents, viscosity modifiers, defoamers, etc., as long as the gas barrier properties and adhesion to the plastic substrate (I) are not significantly impaired. Examples of heat stabilizers, antioxidants, or anti-degradation agents include hindered phenols, phosphorus compounds, hindered amines, sulfur compounds, copper compounds, and alkali metal halides. One or more of these may be used.

[0123] In particular, examples of the reinforcing material include clay, talc, wollastonite, silicon oxide, aluminum oxide, calcium silicate, sodium aluminate, sodium aluminosilicate, magnesium silicate, hollow glass balloons, carbon black, zeolite, montmorillonite, hydrotalcite, fluoromica, metal fiber, metal whisker, ceramic whisker, potassium titanate whisker, boron nitride, graphite, glass fiber, carbon fiber, fullerene (C60, C70, etc.), carbon nanotubes and other inorganic fillers or carbon fillers.

[0124] The total content of these additives is usually set to about 5% by mass or less in the gas barrier layer, but is not limited thereto. It should be noted that, among these additives, when having the same function as any of the above-mentioned polycarboxylic acids, polyols, polyamines, etc. constituting the gas barrier layer, the content of the additive is set to the content of the above-mentioned polycarboxylic acids, etc., and is not included in the "content of the additive".

[0125] In the present invention, the thickness of the gas barrier layer (II) laminated on the plastic substrate (I) is not limited, but is preferably 0.05 μm or more, more preferably 0.10 μm or more, and most preferably 0.15 μm or more from the viewpoint of sufficiently improving the gas barrier properties of the gas barrier layered product after elongation. In addition, from the viewpoint of suppressing the performance degradation of the gas barrier layer (II) or from the viewpoint of economic efficiency, it is preferably 5.00 μm or less, more preferably 1.00 μm or less, and most preferably 0.50 μm or less.

[0126] (2) Layer structure and properties of the laminate of the present invention

[0127] (2-1) Structure of laminate

[0128] The basic structure of the laminate of the present invention comprises a plastic substrate (I) containing a metal-containing layer and a gas barrier layer (II), but as long as the metal-containing layer (M) and the gas barrier layer (II) are in contact, they may each be composed of one layer or two or more layers as described above.

[0129] In particular, when the plastic substrate (I) is a multilayer film, the laminate of the present invention may include other resin-containing layers (R) without particular limitation, as long as the metal-containing layer (M) and the gas barrier layer (II) are in direct contact with each other, as described below.

[0130] a. "(R) / (M) / (II)",

[0131] b. "(M) / (R) / (M) / (II)",

[0132] c. "(II) / (M) / (R) / (II)",

[0133] d. "(II) / (M) / (R) / (M) / (II)"

[0134] In these structures, since at least the gas barrier layer (II) is in contact with the metal-containing layer (M), the polycarboxylic acid in the gas barrier layer (II) and the metal component in the metal-containing layer (M) react easily, and thus gas barrier properties can be effectively obtained. Among them, considering the equipment used for production, operability, etc., the above-mentioned "(R) / (M) / (II)" structure is preferred.

[0135] (2-2) Characteristics of laminated body

[0136] The laminate of the present invention has the following gas barrier properties, etc. In addition, in the measurement of the gas barrier properties, the gas barrier layered product was subjected to a retort treatment at 120° C. for 30 minutes as a measurement sample.

[0137] More specifically, the retort treatment for measuring the gas barrier properties can be performed by spraying 120°C hot water over the entire laminate for 30 minutes in a sealed container. As such a retort treatment apparatus, for example, a commercially available hot water spray type "RCS-100 / 10SPXG manufactured by Nisaka Seisakusho Co., Ltd." can be used.

[0138] (2-2-1) Elastic modulus (complex elastic modulus)

[0139] For the laminate of the present invention, the laminate was subjected to a steaming treatment at 120°C for 30 minutes, and the elastic modulus of the surface of the gas barrier layer (II) of the gas barrier laminate was measured by nanoindentation method to be 9.0 to 12.5 GPa, preferably 9.5 to 12.0 GPa, and more preferably 10.0 to 11.5 GPa. As a result, even if stress such as bending is applied to the gas barrier layer (II), such as in the case of vacuum packaging, excellent gas barrier properties and aroma retention properties can be exerted in a high temperature and high humidity environment. That is, since it has high resistance (flexibility) to bending and the like applied during vacuum packaging, it can exert excellent gas barrier properties and aroma retention properties in a high temperature and high humidity environment. When the elastic modulus is less than 9.0 GPa, the thickness or quality of the gas barrier layer (II) becomes uneven, or the coating may fall off or the cross-linking reaction may not be promoted (poor coating liquid composition of the gas barrier layer (II), etc.). If stress is applied to the gas barrier layer (II), it may not be able to exert excellent gas barrier properties and fragrance retention in a high temperature and high humidity environment. When the elastic modulus exceeds 12.5 GPa, for the same reasons as above, when stress is applied to the barrier layer (II) such as vacuum packaging, it is sometimes impossible to exert excellent gas barrier properties and fragrance retention in a high temperature and high humidity environment. The elastic modulus here is a value measured using a nanoindenter. In addition, the elastic modulus refers to the value when the indenter is pressed into the surface of the gas barrier layer (II) of the gas barrier laminate.

[0140] (2-2-2) Hardness

[0141] The laminate of the present invention is subjected to a 120°C × 30 minute boiling treatment, and the hardness of the surface of the gas barrier layer (II) measured by the nanoindentation method is preferably 0.7 to 1.3 GPa, particularly preferably 0.8 to 1.2 GPa, and most preferably 0.9 to 1.1 GPa. As a result, even when physical stress is applied to the gas barrier layer (II) during vacuum packaging, etc., excellent gas barrier properties and fragrance retention properties can be exerted in a high temperature and high humidity environment. The hardness refers to the value when the indenter is pressed into the gas barrier layer (II) of the gas barrier laminate.

[0142] (2-2-3) Oxygen permeability after elongation (temperature 40°C and humidity 90% RH)

[0143] For the laminate of the present invention, after the laminate was subjected to a steaming treatment at 120°C for 30 minutes, and then stretched by 7% in both the MD direction and the TD direction at a rate of 1.5% / s under a temperature of 35°C and a humidity of 50% RH, the oxygen permeability of the laminate under a temperature of 40°C and a humidity of 90% RH was 100 ml / (m 2 ·day·MPa) or less, preferably 80ml / (m2 ·day·MPa) or less, and the most preferred is 50ml / (m 2 ·day·MPa) or less. Thus, even when physical stress is applied, such as by vacuum packaging, excellent gas barrier properties and aroma retention properties can be exhibited. The lower limit of the above oxygen permeability can be set to 10 ml / (m 2 ·day·MPa), but not limited to.

[0144] The device for stretching after the steaming treatment is not particularly limited. For example, the biaxial stretching device "Karo IV" manufactured by BRUCKNER can be used to stretch 7% simultaneously in MD / TD at a speed of 1.5% / s. The size of the sample used for stretching is not particularly limited, as long as the size (e.g., 10 cm×10 cm) that can measure the oxygen permeability can be used. The temperature and humidity during stretching can be set to 35°C and 50%RH, assuming the working environment of vacuum packaging.

[0145] For example, in a retort product (vacuum-packed food, etc.) in which solid components such as corn are vacuum-packed, the corn is pre-cooked (cooked raw corn) before packaging and then filled into a packaging bag, and then vacuum-packed. Then, the retort treatment is performed for the purpose of sterilization. In the retort treatment process, since heat and pressure are also applied to the packaging bag, the base material strength or gas barrier properties of the packaging bag itself are reduced, and the flexibility is reduced. For the laminate of the present invention, in order to evaluate the gas barrier properties under the harsh treatment conditions as described above, it is also stretched after applying the stress caused by the heat and pressure generated by the retort treatment.

[0146] In particular, in addition to the case where the thickness or quality of the gas barrier layer (II) is not uniform, in the case of peeling, poor cross-linking reaction, etc., due to elongation and / or bending / bending, cracks and other defects are generated locally in the gas barrier layer (II), or the layer is thinned, so the gas barrier properties are extremely reduced. In contrast, even if the laminate is elongated or bent / bent after boiling treatment, the product of the present invention can obtain excellent gas barrier properties and aroma retention properties in harsh environments such as temperature 40°C and humidity 90%RH. In addition, the product of the present invention is a gas barrier laminate that can exhibit excellent gas barrier properties and aroma retention properties in a high temperature and high humidity environment after vacuum packaging even in hot water sterilization (boiling treatment) applications other than boiling treatment.

[0147] (2-2-4) Oxygen permeability before elongation (temperature 40°C and humidity 90% RH)

[0148] The oxygen permeability of the laminate of the present invention after the laminate has been subjected to a retort treatment at 120°C for 30 minutes and before the stretching is generally 50 ml / (m 2 ·day·MPa) or less, preferably 40ml / (m 2 ·day·MPa) or less. The lower limit of the oxygen permeability can be set to, for example, 1 ml / (m 2 ·day·MPa), but not limited to.

[0149] (2-2-5) Oxygen permeability after elongation (temperature 20°C and humidity 90% RH)

[0150] For the laminate of the present invention, after the laminate was subjected to a steaming treatment at 120°C for 30 minutes, and then stretched by 7% in both the MD direction and the TD direction at a rate of 1.5% / s under a temperature of 35°C and a humidity of 50% RH, the oxygen permeability of the laminate under a temperature of 20°C and a humidity of 90% RH was generally 70 ml / (m 2 ·day·MPa) or less, preferably 50ml / (m 2 ·day·MPa) or less. The lower limit of the oxygen permeability can be set to, for example, 1 ml / (m 2 ·day·MPa), but not limited to.

[0151] (2-2-6) Oxygen permeability before elongation (temperature 20°C and humidity 90% RH)

[0152] The oxygen permeability of the laminate of the present invention after the laminate has been subjected to a retort treatment at 120°C for 30 minutes and before the stretching is generally 40 ml / (m 2 ·day·MPa) or less, preferably 35ml / (m 2 ·day·MPa) or less. The lower limit of the oxygen permeability can be set to, for example, 0 ml / (m 2 ·day·MPa), but not limited to.

[0153] (2-2-7) Oxygen permeability after bending (temperature 20°C and humidity 90% RH, temperature 40°C and humidity 90% RH)

[0154] The laminate of the present invention preferably has high gas barrier properties even after bending. More specifically, as shown in Test Example 1 described later, a laminated film (test sample) formed by laminating an unstretched polypropylene film with a thickness of 50 μm on the gas barrier layer of the laminate of the present invention via a two-component curable polyurethane adhesive layer with a thickness of 4 μm is subjected to a Gelbo Flex tester in accordance with ASTM F392 at a temperature of 23°C and a humidity of 50% RH, i.e., a repeated bending fatigue test is performed 10 times. The oxygen permeability of the test sample at a temperature of 20°C and a humidity of 90% RH is generally preferably 50 ml / (m 2 ·day·MPa) or less, and more preferably 40ml / (m 2 ·day·MPa) or less. The lower limit of the oxygen permeability can be set to, for example, 0 ml / (m 2 ·day·MPa) or so, but not limited thereto. In addition, the oxygen permeability of the test sample after the above treatment in an environment of temperature 40°C and humidity 90%RH is usually preferably 100ml / (m 2 ·day·MPa) or less, and more preferably 80ml / (m 2 ·day·MPa) or less, and the most preferred is 50ml / (m 2 ·day·MPa) or less. The lower limit of the oxygen permeability can be set to, for example, 10 ml / (m 2 ·day·MPa), but not limited to.

[0155] (2-2-8) Oxygen permeability evaluation based on images

[0156] As shown in Test Example 1 described later, for the laminate of the present invention, the gas barrier properties can also be evaluated by image processing for the test sample after the same treatment as above. More specifically, using the test sample treated 10 times using the above-mentioned Gelbo Flex tester, a three-side sealed bag with an outer dimension of width 100 mm × height 150 mm made in such a way that the sealing layer becomes the inner surface is filled with a predetermined adjustment liquid (blue), and then sealed by heat sealing. The sealed three-side sealed bag was subjected to a retort treatment at 120°C × 30 minutes. Then, when a photo of the three-side sealed bag was taken on white paper, a portion colored blue was confirmed in the image. This portion is a portion where oxygen permeates due to a defective gas barrier layer (II). Then, the gas barrier properties are evaluated based on the area ratio of the blue portion in the overall area of ​​the photographed three-side sealed bag. The smaller the area ratio, the higher the gas barrier properties. In the gas barrier laminate of the present invention, the area ratio of the blue portion in the above-mentioned evaluation method is generally preferably 0.3% or less, and particularly preferably less than 0.1%.

[0157] (2-2-9) Fragrance retention

[0158] The aroma retention of the laminate of the present invention is also excellent. That is, when the laminate of the present invention is used to seal the contents, the aroma components contained in the contents can be effectively prevented or suppressed from leaking to the outside. Therefore, when food or the like is used as the contents, the aroma of the food or the like can be maintained for a long time. The aroma retention in the present invention can be evaluated by the method shown in Test Example 1 described later. In the aroma retention based on this method, the concentration of leaked ethanol is preferably less than 0.1% by mass, and particularly more preferably less than 0.5% by mass.

[0159] (2-2-10) Tensile strength

[0160] The tensile strength of the laminate of the present invention in a tensile test measured under a temperature of 23° C. and a humidity of 50% RH according to Japanese Industrial Standard “JIS K7127” is preferably 150 MPa or more, and more preferably 180 MPa or more. If the tensile strength is less than 150 MPa, there is a tendency that the mechanical strength is insufficient and the puncture strength is reduced. Therefore, for example, it can be set to about 150 to 300 MPa, but is not limited thereto.

[0161] (2-2-11) Tensile elongation

[0162] From the same viewpoint as the tensile strength, the tensile elongation of the laminate of the present invention in the tensile test measured in accordance with Japanese Industrial Standard "JIS K7127" at a temperature of 23°C and a humidity of 50%RH is preferably 60% or more, and more preferably 80% or more. Therefore, for example, it can be set to about 60 to 95%, but is not limited thereto.

[0163] (2-2-12) Transparency

[0164] Regarding the transparency of the laminate of the present invention, the haze measured in accordance with Japanese Industrial Standard "JIS K7136" at a temperature of 23°C and a humidity of 50%RH is preferably 70% or less, more preferably 50% or less, further preferably 30% or less, particularly preferably 15% or less, and most preferably 10% or less. However, depending on the application, transparency is sometimes not required, so it is not limited thereto. The lower limit of the haze can be, for example, 1%, but is not limited thereto.

[0165] (2-2-13) Pinhole resistance

[0166] Regarding the pinhole resistance of the laminate of the present invention, the number of pinholes generated in the 500 repeated bending fatigue test at 5°C is preferably 100 or less, and particularly preferably 20 or less. The above-mentioned pinhole resistance is obtained by measuring and evaluating the number of pinholes generated after 500 bendings at 5°C using a Gelbo Flex tester (e.g., manufactured by TESTERSANGYO) in accordance with ASTM F392. The closer the lower limit of the number of pinholes generated is to 0, the more preferred it is, for example, it can be set to 0, but is not limited to this. It should be noted that the sample (measurement area) of the laminate used in the pinhole resistance evaluation is 27 cm×20 cm.

[0167] (2-2-14) Thickness

[0168] The total thickness (total thickness) of the laminate of the present invention is 100 μm or less, and can be appropriately set within this range according to the purpose, etc. From the viewpoints of reducing the amount of material used and bag making properties, the thinner the total thickness, the better, and it is particularly preferably 50 μm or less, and most preferably 30 μm or less. In addition, from the viewpoint of barrier properties, the thicker the total thickness, the better, and it is particularly preferably 5 μm or more, and more preferably 10 μm or more. Therefore, for example, it can be set within the range of 5 to 100 μm.

[0169] 2. Method for producing gas barrier layered product

[0170] The laminate of the present invention can be produced by any method as long as it has the above-mentioned characteristics. In particular, the laminate of the present invention can be suitably produced by the following production method, which is a method for producing a gas barrier laminate, comprising:

[0171] (1) a step of preparing a raw material solution (raw material solution preparation step), wherein the raw material solution comprises a polycarboxylic acid, a mineral oil and an acetylene glycol-based nonionic surfactant, wherein the mass ratio of the mineral oil to the acetylene glycol-based nonionic surfactant is 80 / 20 to 40 / 60; and

[0172] (2) A step of applying the raw material liquid as a coating liquid for forming a gas barrier layer (II) onto at least the surface of the metal-containing layer of a plastic substrate (I) comprising a metal-containing layer containing at least one of a metal and a metal compound and a resin component (coating step).

[0173] Raw material liquid preparation process

[0174] In the raw material liquid preparation step, a raw material liquid containing a polycarboxylic acid, a mineral oil, and an acetylene glycol-based nonionic surfactant is prepared, wherein the mass ratio of the mineral oil to the acetylene glycol-based nonionic surfactant is 80 / 20 to 40 / 60.

[0175] From the perspective of workability, the raw material liquid is preferably aqueous (a liquid in which the solvent is an aqueous solvent). Therefore, the polycarboxylic acid, and the optional components such as polyols and polyamines are preferably water-soluble or water-dispersible, and more preferably water-soluble.

[0176] As the polycarboxylic acid, various polycarboxylic acids listed in the above “1. Gas barrier layered product” can be used. In addition, as the polyol, the polyols listed in the above “1. Gas barrier layered product” can also be used.

[0177] As the raw material liquid, an aqueous solution or aqueous dispersion of a polycarboxylic acid obtained by mixing a polycarboxylic acid with water can be used. The concentration of the polycarboxylic acid in this case is not limited, and may be, for example, within a range of about 5 to 30% by mass in the raw material liquid.

[0178] In addition, when a polyol is used in combination to prepare an aqueous raw material liquid, the type of polyol used, the ratio of polycarboxylic acid to polyol, additives, etc., may be in accordance with the description of "1. Gas barrier laminate" above. In this case, it is preferred to add 0.1 to 20 equivalent % of an alkali compound relative to the carboxyl group of the polycarboxylic acid. If the content of the carboxyl group of the polycarboxylic acid is high, the hydrophilicity becomes high, so an aqueous solution can be made even without adding an alkali compound. In this case, by adding an appropriate amount of an alkali compound, the gas barrier properties of the obtained gas barrier laminate can be significantly improved.

[0179] As the above-mentioned alkaline compound, any one can be used as long as it can neutralize the carboxyl group of the polycarboxylic acid. For example, at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, sodium carbonate, ammonia water, sodium bicarbonate, etc. can be cited. From the viewpoint of enhancing gas barrier properties, the addition amount (neutralization degree) of the alkaline compound is usually preferably 0.1 to 20 mol% relative to the carboxyl group of the polycarboxylic acid.

[0180] In the present invention, when a polycarboxylic acid and a polyamine are mixed to prepare an aqueous coating liquid, it is preferred to add a base to the polycarboxylic acid in advance in order to suppress gelation.

[0181] As the above-mentioned base, any base can be used as long as it does not hinder the gas barrier properties of the obtained gas barrier laminate. For example, inorganic compounds such as sodium hydroxide, calcium hydroxide, ammonia, and organic compounds such as methylamine and diethanolamine can be cited. They can be used in one or more kinds. Among them, ammonia is preferred from the perspective of easy volatilization during drying and heat treatment. From the viewpoint of inhibiting the gelation of the coating liquid, the amount of base added is usually preferably 0.6 equivalents or more relative to the carboxyl group of the polycarboxylic acid, and particularly preferably 0.7 equivalents or more, and most preferably 0.8 equivalents or more.

[0182] In the production method of the present invention, the mineral oil has a function of homogenizing the coating liquid for forming the gas barrier layer (II) described later, and can contribute to improving the gas barrier properties and the aroma retention properties by being evenly distributed.

[0183] Mineral oil is not particularly limited as long as it is a hydrocarbon mixture derived from petroleum containing hydrocarbons, and for example, at least one hydrocarbon mineral oil of aromatic hydrocarbons, paraffin hydrocarbons, cycloparaffin hydrocarbons, etc. can be suitably used. Among them, it is preferred that the average carbon number is 20 or more and 35 or less and is liquid at normal temperature and pressure. They can also use commercial products. As commercial products, for example, "AGITAN282" (MUNZING CHEMIE GmbH), "SN DEFOAMER 154S" (San Nopco) and the like can be used.

[0184] When adding mineral oil, in addition to water, silica particles, polyoxyalkylene compounds, (meth)acrylic acid / (meth)acrylic acid alkyl ester copolymer (salt), and emulsifiers, known additives (antifreeze agents, water repellents, film formation regulators, etc.), solvents, etc. may be used in combination as needed.

[0185] The amount of mineral oil added is not limited, but is preferably added in an amount of 0.005 to 0.15 parts by mass, more preferably 0.007 to 0.050 parts by mass, and most preferably 0.010 to 0.020 parts by mass, relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the raw material liquid.

[0186] The acetylene glycol-based nonionic surfactant also has a function of homogenizing the coating liquid for forming the gas barrier layer (II), and can contribute to improving the gas barrier properties and the aroma retention properties by making the coating liquid uniformly distributed.

[0187] As the acetylene glycol nonionic surfactant, at least one of acetylene glycol compounds and polyoxyethylene adducts thereof can be suitably used. Basically, it is a nonionic surfactant having an acetylene group disposed in the center of the molecule and having a bilaterally symmetrical structure with the acetylene group as the center, for example, a compound having an acetylene glycol represented by the following general formula (1) as a basic structure.

[0188]

Chemical formula 1

[0189]

[0190] (In which, R 1 and R 2 are the same as or different from each other and represent methyl, propyl or isopropyl. 3 and R 4 The same as or different from each other represent a hydroxyl group or a polyoxyethylene group. ).

[0191] More specifically, at least one of 3,6-dimethyl-4-decyne-3,6-diol, 2,4,7,9-tetramethyl-5-decyne-diol, 2,4,7,9-tetramethyl-5-decyne-diol-dipolyoxyethylene ether and the like can be exemplified. Of these compounds, ethylene oxide (EO) adducts are preferred. The content of the ethylene oxide part of the EO adduct is not limited, but is generally about 20 to 85% by mass, preferably 40 to 65% by mass.

[0192] Commercially available acetylene glycol nonionic surfactants may be used, such as "OLFINE E1004", "OLFINE E1004C", "OLFINE E1006", "OLFINE E1010", "OLFINE E1020", "SURFYNOL 420", "SURFYNOL 440" (all manufactured by Nissin Chemical Industry Co., Ltd.).

[0193] The acetylene glycol nonionic surfactant is preferably added in an amount of 0.005 to 0.100 parts by mass, more preferably 0.007 to 0.050 parts by mass, and most preferably 0.010 to 0.020 parts by mass, relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the raw material liquid.

[0194] The acetylene glycol nonionic surfactant in the coating liquid for forming the gas barrier layer (II) may volatilize due to heat treatment after coating on the plastic substrate (I) depending on its type, and may not remain in the formed gas barrier layer (II).

[0195] When the raw material liquid contains mineral oil and acetylene glycol nonionic surfactant, one of the most important conditions is the mixing ratio of the mineral oil and the acetylene glycol nonionic surfactant.

[0196] From the viewpoint of improving elongation or bending / folding resistance, the mixing ratio (mass ratio) of mineral oil to acetylene glycol nonionic surfactant is preferably in the range of 80 / 20 to 40 / 60 of mineral oil / acetylene glycol nonionic surfactant, particularly preferably 75 / 25 to 45 / 55, further preferably 70 / 30 to 50 / 50, and most preferably 65 / 35 to 55 / 45.

[0197] The mixing ratio of mineral oil and acetylene glycol nonionic surfactant also affects the elastic modulus of the gas barrier layer (II). When the mixing ratio of mineral oil exceeds 80, the elastic modulus of the gas barrier layer (II) tends to increase, and sometimes exceeds 12.5 GPa, which is the upper limit of the elastic modulus specified in the present invention. On the other hand, when the mixing ratio of mineral oil is less than 40, the elastic modulus of the gas barrier layer (II) tends to decrease, and sometimes does not meet the lower limit of the elastic modulus specified in the present invention, which is 9.0 GPa.

[0198] The raw material liquid may contain other additives within a range that does not hinder the effects of the present invention. Examples of the additives include the various additives listed in the above-mentioned "1. Gas barrier layered product".

[0199] The raw material solution can be suitably prepared by mixing these components on the basis of using at least an aqueous solvent as a solvent. In this case, mixing can be performed using a dissolving kettle equipped with a stirrer. As the aqueous solvent, 1) water or 2) a mixed solvent of water and a water-soluble organic solvent can be used. As the water-soluble organic solvent, there is no limitation, for example, monohydric alcohols such as methanol and ethanol, polyhydric alcohols such as diethylene glycol and glycerol, etc. can be used.

[0200] The mixing step is not limited, and in particular, when adding a polyol, it is preferred to prepare the polycarboxylic acid and the polyol in aqueous solution and mix them before coating. In this case, if the above-mentioned alkaline compound is added to the aqueous solution of the polycarboxylic acid in advance, the stability of the aqueous solution can be improved.

[0201] In the present invention, as a method for making the raw material liquid (gas barrier layer (II) forming coating liquid) contain mineral oil, a method of preparing a pre-dispersion liquid and using it to prepare the raw material liquid can be preferably adopted. For example, a pre-dispersion liquid obtained by diluting the mineral oil with an aqueous solution or dispersion containing a polycarboxylic acid can be used. In this way, the mineral oil (and the acetylene glycol-based nonionic surfactant) can be more uniformly dispersed in the gas barrier layer (II) forming coating liquid, and as a result, a gas barrier laminate that can exert more excellent gas barrier properties and fragrance retention properties can be provided.

[0202] The method for preparing the pre-dispersion liquid is not limited, and examples thereof include: (a) a method in which a mixed liquid (mixed liquid a') containing no mineral oil and no acetylene glycol nonionic surfactant is prepared separately from a mixed liquid (mixed liquid a) containing a polycarboxylic acid and not containing mineral oil and no acetylene glycol nonionic surfactant, a pre-dispersion liquid is prepared by using the mixed liquid a' and adding mineral oil (or mineral oil and no acetylene glycol nonionic surfactant), and then the mixed liquid a is mixed with the pre-dispersion liquid; (b) a method in which a portion of the mixed liquid a is collected, a pre-dispersion liquid is prepared using the collected mixed liquid a2, and then the remaining mixed liquid a1 of the mixed liquid a is mixed with the pre-dispersion liquid, etc.

[0203] Regarding the ratio of the mixed liquid used to prepare the pre-dispersion liquid, from the viewpoint of being able to more reliably disperse the mineral oil, in either of the above-mentioned cases (a) and (b), when the total amount of the mixed liquid contained in the raw material liquid is set to 100 mass %, it is usually preferably set to about 0.05 to 15 mass %, and particularly preferably to 0.1 to 5 mass %. In the above-mentioned case (a), the above-mentioned total amount is the total amount of the mixed liquid a and the mixed liquid a'. In the above-mentioned case (b), the above-mentioned total amount is the total amount of the mixed liquid a1 and the mixed liquid a2.

[0204] In the present invention, the method (b) is preferred from the viewpoints of ease of composition control of the mixed solution, production efficiency, etc. More specifically, a method including the following steps can be suitably adopted: 1) a part (mixed solution a2) of a mixed solution (mixed solution a) containing a polycarboxylic acid and not containing mineral oil and acetylene glycol nonionic surfactant is collected, and mineral oil (or mineral oil and acetylene glycol nonionic surfactant) is added to the collected mixed solution a2 to prepare a pre-dispersion solution; 2) the remaining part of the mixed solution (mixed solution a1) is mixed with the pre-dispersion solution to prepare a coating solution for forming a gas barrier layer (II). In this case, the mixed solution a1 may contain mineral oil and acetylene glycol nonionic surfactant, but preferably does not contain mineral oil and acetylene glycol nonionic surfactant. In addition, the mixed solution a2 may be collected in two or more parts to prepare pre-dispersion solutions respectively. For example, it may be divided into mixed solution a2 (1), mixed solution a2 (2), mixed solution a2 (3) ... mixed solution a2 (n).

[0205] The content of the mineral oil in the preliminary dispersion is not limited as long as it is 0.005 to 0.15 parts by mass relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the raw material liquid (or the coating liquid for forming the gas barrier layer (II)). From the viewpoint of avoiding content error or improving dispersibility, the content may be adjusted to 0.1 to 15 parts by mass (preferably 0.5 to 13 parts by mass, more preferably 1 to 12 parts by mass) relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the preliminary dispersion.

[0206] The agitator used for pre-dispersion is not particularly limited, and examples thereof include blade-type agitators, high-speed rotary homogenizers, high-pressure homogenizers, and dissolvers. High-speed rotary homogenizers, high-pressure homogenizers, and dissolvers are particularly preferred, and high-speed rotary homogenizers are more preferred. The device and stirring conditions used for dispersion are not particularly limited as long as they fall within the range of the median particle size measured by the particle size distribution described later, and for example, it is preferred to pre-disperse the mixture at a rotation speed of 2000 to 8000 rpm for 5 to 30 minutes using a high-speed rotary homogenizer.

[0207] In addition, the method for making the coating liquid for forming the gas barrier layer (II) contain an acetylene glycol nonionic surfactant is not particularly limited, and the dispersion of the mineral oil can be improved by mixing and dispersing the acetylene glycol nonionic surfactant together with the mineral oil. Therefore, it is preferred to mix the acetylene glycol nonionic surfactant when dispersing the mineral oil. Therefore, in the case of mixing the mineral oil by the above-mentioned pre-dispersion, it is also preferred to mix the acetylene glycol nonionic surfactant together with the mineral oil.

[0208] The content of the acetylene glycol-based nonionic surfactant in the preliminary dispersion is not limited as long as it is 0.005 to 0.100 parts by mass relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the raw material solution (or the coating solution for forming the gas barrier layer (II)). However, from the viewpoint of improving the elongation or the resistance to bending / folding, it can be adjusted to 0.01 to 20 parts by mass (preferably 0.05 to 15 parts by mass, more preferably 0.1 to 10 parts by mass) relative to 100 parts by mass of the total (solid content) of the polycarboxylic acid and the polyol in the preliminary dispersion.

[0209] The prepared pre-dispersion liquid can be mixed with the mixed liquid containing polycarboxylic acid and not containing mineral oil and acetylene glycol nonionic surfactant to obtain the raw material liquid. In the case of (a) above, the mixed liquid is equivalent to the mixed liquid a. In the case of (b) above, the mixed liquid is equivalent to the mixed liquid a1. The method of mixing the two is not particularly limited, and can be implemented according to the apparatus and conditions that can be used in the above-mentioned pre-dispersion.

[0210] The obtained raw material liquid can be directly used as a coating liquid for forming a gas barrier layer (II) for coating on a plastic substrate, or it can be provided to a filtering treatment step before the coating. Preferably, the coating liquid for forming a gas barrier layer (II) can be appropriately prepared by passing the raw material liquid through a filter with a filtration accuracy (absolute filtration accuracy) of 1.0 to 10.0 μm. Surprisingly, by the above-mentioned coating liquid preparation step, a film that can exert high gas barrier properties can be obtained, especially in a high temperature and high humidity environment such as a temperature of 40°C and a humidity of 90% RH. The reason is not yet clear, but according to the applicant's subsequent speculation, it is considered as follows. By passing it through a filter, the bubbles contained in the raw material liquid can be subdivided and the coarse particles can be removed. In addition, the aggregates of the polycarboxylic acid and / or polyol in the raw material liquid are subdivided, and the reaction of the polycarboxylic acid with the polyol, and the polycarboxylic acid with the metal component is more likely to occur more densely when forming the gas barrier layer. As a result, the gas barrier layer (II) is homogeneous as a whole, and a gas barrier layer (II) without defects such as pores and cracks is formed.

[0211] From the viewpoint of suppressing the repellency or fall-off of the coating liquid and forming a uniform gas barrier layer (II), a filter with a filtration accuracy of 1.0 to 10.0 μm is used as the filter, and a filter with a filtration accuracy of 2.0 to 5.0 μm is more preferred.

[0212] In addition, in the present invention, in order to improve the filtration efficiency and filtration performance, it is preferred to pressurize the raw material liquid while passing it through the filter. The pressure is usually set in the range of 0.1 to 0.3 MPa, and is particularly preferably set to 0.15 to 0.25 MPa. If the pressure is less than 0.1 MPa, the filtration efficiency is low. On the other hand, when the pressure is greater than 0.3 MPa, there is a concern that the filter will be damaged. In the present invention, as a pressurizing means, a conventional pressurizing device (pump, etc.) can be used.

[0213] The filter device is not particularly limited as long as the filtration accuracy is within the range of 1.0 to 10.0 μm. For example, a filter device including (a) a filter housing, (b) a filter disposed in the filter housing, and (c) a pump for pressurizing the raw material liquid into the filter can be used.

[0214] As a filter (cartridge filter), for example, a filter made of any material such as a metal mesh, a filter cloth, a nonwoven fabric laminate, a resin molded body, a ceramic molded body, etc. can be suitably used. In addition, its shape is not limited, for example, a cylindrical filter (fish cake (Japanese original text: ちくわ) shape) can be used. Regarding the size, for example, if it is a cylindrical shape, it can be set to an outer diameter of about 50 to 100 mm, an inner diameter of about 10 to 30 mm, and a length of about 200 to 1000 mm, but it is not limited to this. These devices can also use known or commercially available devices.

[0215] The treatment method using the filter may be any of a continuous method and a cyclic method. In addition, the number of times of passing through the filter may be one time or two or more times (multi-stage method). Therefore, for example, a method may be adopted in which, after passing through a first filter having a filtration accuracy within a range of 1.0 to 10.0 μm, the filter passes through a second filter having a filtration accuracy within a range of 1.0 to 10.0 μm and having a smaller filtration accuracy than the first filter.

[0216] In the present invention, the viscosity of the coating liquid when passing through the filter is not particularly limited, and the viscosity when measured using a B-type viscometer at a liquid temperature of 25° C. is preferably in the range of 5.0 to 50.0 mPa·s. By setting the viscosity of the liquid before passing through the filter to within the above range, the subdivision of bubbles can be further promoted. In addition, the effect of promoting the subdivision of the agglomerates of polycarboxylic acids and / or polyols can also be expected. Therefore, in the case where the viscosity of the coating liquid before passing through the filter is outside the above range, the viscosity of the coating liquid can also be adjusted as needed.

[0217] In the present invention, the coating liquid for forming the gas barrier layer (II) is usually in the form of an aqueous dispersion (emulsion or dispersion) in which the solvent is an aqueous solvent. The size of the droplets at this time is not limited. From the perspective of the homogeneity of the gas barrier layer (II), the median particle size (D50) is usually preferably 0.1 to 0.6 μm, more preferably 0.15 to 0.55 μm, and most preferably 0.2 to 0.5 μm. When the median particle size is less than 0.1 μm, when the raw material liquid is passed through the filter, the possibility of the mineral oil or acetylene glycol nonionic surfactant being removed or adsorbed on the filter is high, and a homogeneous gas barrier layer (II) may not be obtained. As a result, high gas barrier properties cannot be obtained under the environment of temperature 40°C and humidity 90% RH after elongation, and elongation and / or bending and bending occur locally, thereby sometimes further reducing the gas barrier properties. In addition, when the median particle size exceeds 0.6 μm, even if the raw material liquid passes through the filter, the coagulation or dissolved residue of the polycarboxylic acid and / or polyol in the raw material liquid and the coagulation of the mineral oil will pass through the filter, causing the coating liquid to be repelled or the coating to fall off. In this case, since a uniform gas barrier layer (II) cannot be obtained, high gas barrier properties cannot be obtained under the environment of temperature 40°C and humidity 90% RH after elongation.

[0218] Coating process

[0219] In the coating step, the gas barrier layer-forming coating liquid is coated on at least the surface of the metal-containing layer of the plastic substrate (I) comprising the metal-containing layer containing at least one of a metal and a metal compound and a resin component.

[0220] The plastic substrate (I) includes a metal-containing layer containing at least one of a metal and a metal compound and a resin component, and can adopt the structure described in the above-mentioned "1. Gas barrier laminate". In particular, a plastic substrate configured in a manner that the metal-containing layer is exposed can be suitably used. As such a substrate, for example, a film preformed from a raw material containing a resin can be used. In addition, the method for producing the plastic substrate (I) is not particularly limited, and for example, a plastic substrate (I) produced by the following operation can also be used.

[0221] In the case of a plastic substrate (I) composed of a single-layer film, for example, a thermoplastic resin mixed with a metal component is melted by heating in an extruder, extruded from a T-die into a film, and cooled and solidified on a rotating cooling drum by a known casting method such as an air knife casting method and an electrostatic application casting method to obtain an unstretched film. This can be used as the plastic substrate (I).

[0222] In addition, in the case of a plastic substrate (I) formed of a film composed of multiple layers, for example, a thermoplastic resin mixed with a metal component is heated and melted in an extruder A, and a thermoplastic resin is heated and melted in an extruder B, and the two melted resins are overlapped in a die head, and a film having a two-layer structure, such as a metal-containing layer (M) / resin layer (R), is extruded from a T die, and cooled and solidified in the same manner as above, thereby obtaining a film in an unstretched state. The film thus obtained can be used as a plastic substrate (I). In each of these methods, by making the plastic substrate (I) contain a metal, the step of laminating the layer containing the metal component on the substrate can also be omitted.

[0223] If necessary, the plastic substrate (I) before being coated with the coating liquid for forming the gas barrier layer (II) may be subjected to a surface treatment such as a corona discharge treatment. These treatment methods themselves can be carried out according to known methods.

[0224] The method for applying the coating liquid for forming the gas barrier layer (II) to the plastic substrate (I) is not particularly limited. For example, one or a combination of two or more of an air knife coater, a kiss roll coater, a metering bar coater, a gravure roll coater, a reverse roll coater, a dip coater, a die coater, etc. can be used.

[0225] After the coating liquid for forming the gas barrier layer (II) is applied to the plastic substrate (I), a drying step of drying the coating film may be performed as necessary.

[0226] The drying method is not particularly limited, and examples thereof include a) a method in which a heat treatment is performed immediately after coating, thereby simultaneously forming a dry film and performing a heat treatment; b) a method in which, after coating, a dry film is formed by evaporating water or the like by blowing hot air from a dryer or the like, irradiating with infrared rays, or the like, and then performing a heat treatment.

[0227] In the present invention, it is preferred to perform the heat treatment immediately after coating unless the physical properties such as the state and gas barrier properties of the gas barrier layer (II) are impaired.

[0228] The heat treatment method is not particularly limited, and a method of heat treatment in a dry atmosphere such as an oven can be cited. In consideration of shortening the process, it is preferred to stretch the plastic substrate (I) after applying the coating liquid for forming the gas barrier layer (II). In any of the above cases, the plastic substrate (I) formed with the gas barrier layer (II) is preferably heat treated for 5 minutes or less in a heating atmosphere at 100° C. or higher.

[0229] In addition, when the gas barrier layer (II) contains a polycarboxylic acid and a polyol, the heat treatment temperature after applying the coating liquid cannot be generalized because it is also affected by the ratio of these, the presence or absence of additive components, the content of additives, etc., and is usually preferably 100 to 300° C., particularly preferably 120 to 250° C., further preferably 140 to 240° C., and most preferably 160 to 220° C. If the heat treatment temperature is less than 100° C., the crosslinking reaction of the polycarboxylic acid and the polyol cannot be sufficiently carried out, and it may be difficult to obtain a laminate having sufficient gas barrier properties. On the other hand, if the heat treatment temperature exceeds 300° C., the gas barrier layer (II) may become brittle.

[0230] The heat treatment time is usually preferably set to 5 minutes or less, more preferably 1 second to 5 minutes, further preferably 3 seconds to 2 minutes, and most preferably 5 seconds to 1 minute. If the heat treatment time is too short, the crosslinking reaction cannot be fully carried out, and it is difficult to obtain a laminate with gas barrier properties. On the other hand, if the heat treatment time is too long, the productivity is reduced.

[0231] The coating liquid for forming the gas barrier layer (II) applied to the plastic substrate (I) may be subjected to high energy ray irradiation treatment such as ultraviolet rays, X-rays, electron beams, etc. before or after the above drying, as required. In such a case, a component that crosslinks or polymerizes by irradiation with high energy rays may be added.

[0232] Stretching process

[0233] In the present invention, the stretching step preferably further includes a step of subjecting the laminate coated with the gas barrier layer-forming coating liquid to simultaneous biaxial stretching or sequential biaxial stretching.

[0234] Stretching method can be any kind in biaxial stretching simultaneously or biaxial stretching successively, and biaxial stretching method simultaneously is particularly preferably used. Biaxial stretching method simultaneously can usually take into account practical characteristics such as mechanical properties, optical properties, thermal dimensional stability, pinhole resistance. In addition, in the biaxial stretching method successively that is stretched transversely after longitudinal stretching, the stretchability of the thermoplastic resin during transverse stretching is reduced due to the orientation crystallization of the film during longitudinal stretching, thus, when the amount of metal components is many, there is a trend that the fracture frequency of the film becomes higher. Therefore, in the present invention, it is preferably implemented to absorb water, adopting biaxial stretching method simultaneously.

[0235] In the case of simultaneous biaxial stretching, for example, a coating liquid for forming a gas barrier layer (II) is coated on a plastic substrate (I), and after the gas barrier layer (II) is formed, simultaneous biaxial stretching is performed in the longitudinal direction (MD) and the transverse direction (TD) using a tenter-type simultaneous biaxial stretching machine, thereby obtaining a gas barrier laminate that has been simultaneously biaxially stretched.

[0236] In the case of performing sequential biaxial stretching, for example, the obtained unstretched film is stretched in the longitudinal direction (MD), and then a coating liquid for forming a gas barrier layer (II) is applied by the above-mentioned method to form a gas barrier layer (II), and then stretched in the transverse direction (TD), thereby obtaining a gas barrier layered product that has been sequentially biaxially stretched.

[0237] If the unstretched film is oriented, stretchability may be reduced in a subsequent step, and therefore the unstretched film is preferably in a substantially amorphous and non-oriented state.

[0238] When a polyamide resin is used as the plastic substrate (I), it is preferred to implement a process (water absorption treatment) for making the unstretched film absorb water before stretching. By implementing such a treatment, the tensile stress is increased, and failures such as film cutting can be more effectively avoided. The method of water absorption treatment is not limited as long as it can make the unstretched film absorb a certain amount of water, for example, it can be any of a) a method of immersing the unstretched film in water; b) a method of spraying water on the unstretched film, etc. In particular, from the perspective of being able to absorb water more effectively, the above-mentioned method a) is preferred, and the method of immersing the unstretched film in warm water at about 30 to 80°C is more preferred. The amount of water absorbed can be set to, for example, about 0.5 to 15 parts by mass of water (i.e., a water absorption rate of 0.5 to 15%) relative to 100 parts by mass of the unstretched film, but it is not limited thereto. The immersion time is not limited, as long as it is set to a time sufficient to implement the above-mentioned amount of water absorption. As a more specific method of water absorption treatment, for example, the unstretched film is preferably transferred to a water tank adjusted to a temperature of 80° C. or less, and immersed in water for less than 5 minutes (e.g., about 30 seconds to 5 minutes), thereby absorbing water in a manner to achieve a water absorption rate of 0.5 to 15% relative to the weight of the unstretched film.

[0239] The stretch ratio of the film is preferably set to 1.5 times or more in the case of uniaxial stretching, and is also preferably set to 1.5 times or more in the longitudinal and transverse directions in the case of biaxial stretching in the longitudinal and transverse directions. It can be set to about 1.5 to 4 times in the MD direction and about 1.5 to 4 times in the TD direction. In addition, the area ratio during biaxial stretching in the longitudinal and transverse directions is not limited, but is usually preferably set to 3 times or more, and is particularly preferably set to 6 to 20 times, among which it is most preferably set to 6.5 to 13 times. On the other hand, the stretch ratio ratio (MD stretch ratio / TD stretch ratio) during biaxial stretching in the longitudinal and transverse directions is not limited, and is preferably set to 1 / 3 to 3 / 1, and is more preferably set to 1 / 2.5 to 2.5 / 1. If the stretch ratio is within this range, a gas barrier laminate with better mechanical properties can be obtained.

[0240] The stretching temperature is also not limited, and can be, for example, carried out in the range of 40 to 220° C. In particular, in the case of sequential stretching, it is preferred that the stretching in the MD direction is 40 to 80° C., and the stretching in the TD direction is 80 to 150° C. In the case of simultaneous biaxial stretching, it is preferably 160 to 220° C.

[0241] The film that has undergone the stretching treatment process may also be subjected to a heat setting process, a relaxation process, etc. as required. In this case, the temperature in the heat setting process can be appropriately set generally within the range of about 150 to 300° C., for example, it can also be set to 200 to 230° C. The time of the heat setting process can generally be changed within the range of about 1 to 30 seconds according to the temperature, etc., for example, it can be set to 1 to 5 seconds, but is not limited thereto.

[0242] In addition, the relaxation process usually only needs to relax in the longitudinal and / or transverse directions within a relaxation rate range of about 0 to 10% (preferably 2 to 6%). The temperature in the relaxation process can be appropriately set within a range of about 150 to 300°C as in the heat setting process, but in order to more reliably achieve a reduction in thermal shrinkage, it is preferably performed at a temperature lower than the highest temperature of the heat setting process. The heat setting process and the relaxation process are preferably performed continuously after heat setting in a tentering machine that has performed a stretching process, for example.

[0243] The laminate of the present invention may be subjected to a humidification treatment after any of the steps such as the stretching treatment step, the heat fixing step, and the relaxation step, as required, in addition to the above-mentioned water absorption treatment, in particular for the purpose of improving the gas barrier properties. The humidification treatment can further promote the reaction between the metal component of the plastic substrate (I) and the polycarboxylic acid of the gas barrier layer (II). Such humidification treatment is not limited, and examples thereof include a) exposing the laminate to an atmosphere of high temperature and high humidity; b) directly contacting the laminate with high temperature water, etc. The humidification treatment conditions vary depending on the composition of the laminate, the treatment method, etc., and when placed in a high temperature and high humidity atmosphere, it is preferably set to a temperature of 30 to 130°C and a humidity of 50 to 100%RH. In the case of contact with high temperature water, it is also preferred to set the temperature to about 30 to 130°C (100°C or more under pressure). The humidification treatment time varies depending on the treatment conditions, etc., but in any case, it can generally be appropriately set within the range of several seconds to several hundred hours.

[0244] The laminate of the present invention may be subjected to surface treatment such as corona discharge treatment as necessary. These treatment methods themselves can be carried out according to known methods.

[0245] 3. Application of gas barrier laminates

[0246] In the present invention, other layers may be stacked for use as long as the effect of the present invention is not hindered. Such a laminate is also included as the laminate of the present invention. As other layers, there are no particular limitations, and examples thereof include base layers such as polyester and polyamide, sealing layers, barrier layers, antistatic layers, release layers, printing layers, etc. One or more of these layers may be used.

[0247] The resin used as the sealant layer may include at least one of low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene, polyethylene / polypropylene copolymer, ethylene-vinyl acetate copolymer, ionomer resin, ethylene-acrylic acid / methacrylic acid copolymer, ethylene-acrylic acid / methacrylate copolymer, polyvinyl acetate resin, etc. Among them, polyolefin resins such as polyethylene, polypropylene, polyethylene / polypropylene copolymer, etc., which have high heat-sealing strength or material strength, are preferred.

[0248] These resins can be used alone, or can be copolymerized or melt-mixed with other resins, or can be acid-modified. There is no limitation on the method of forming a sealing layer on the gas barrier laminate, and examples thereof include a) laminating a film or sheet made of a sealing resin on the gas barrier laminate with the aid of an adhesive; b) extrusion laminating a sealing resin on the gas barrier laminate, etc. In the former method, the film or sheet made of the sealing resin can be in an unstretched state or in a low-ratio stretched state, but the unstretched state is preferred for practical use.

[0249] The thickness of the sealing layer is not particularly limited, but is preferably 20 to 100 μm, and more preferably 40 to 70 μm.

[0250] As the barrier layer (barrier layer other than the gas barrier layer of the laminate of the present invention), a barrier layer used in a known film can be used. For example, a polyvinylidene chloride copolymer layer can be used as the barrier layer.

[0251] The laminate of the present invention can be suitably used as a packaging material accompanied by hot water sterilization such as boiling or retorting in vacuum packaging applications where local elongation stress and / or bending are easily generated during packaging. In addition, since the laminate can exhibit excellent gas barrier properties and aroma retention even in a high temperature and high humidity environment that reduces gas barrier properties, it is also suitable for long-distance transportation of contents such as food or deoxidizers that may suffer from discoloration and inactivation due to oxidation.

[0252] In addition to the above-mentioned contents, in the case where a heat treatment process using hot water or steam is required after filling and packaging, for example, in addition to food and beverages, fruits, fruit juices, drinking water, alcoholic beverages, cooked foods, seafood kneaded products, frozen foods, meat products, boiled foods, bamboo shoots, corn, pickled vegetables, mochi, liquid soups, seasonings, etc., it can also be used for various foodstuffs (Japanese original text:飲食料品), liquid detergents, cosmetics, chemical products and other contents.

[0253] When using the laminate of the present invention as a packaging bag, its form is not limited. For example, it can also be applied to any of double-sided sealed bags, three-sided sealed bags, three-sided sealed bags with a zip-lock, back-sealed bags, gusset bags, bottom-folded bags, stand-up bags, stand-up bags with a zip-lock, double-sided sealed bags, square-bottomed gusset bags, side-sealed bags, bottom-sealed bags, etc., as well as lid materials for cup containers (cup products), deep-drawn packaging (Japanese original text:絞り包装), etc. These packaging bags (the packaging bags of the present invention) are also included in the present invention.

[0254] In particular, even when the packaging bag of the present invention contains a solid component having irregularities on the surface (such as surface irregularities with a step difference of 1 mm or more), such as corn, and is made into a vacuum-packed product, through its vacuum pumping, the packaging bag of the present invention (the laminate of the present invention) will conform to the irregular surface. In such a case, it also has durability against the elongation stress and / or bending stress received by the laminate of the present invention, and thus higher gas barrier properties and aroma retention properties can be obtained. Therefore, the present invention also includes a vacuum-packed product formed by at least containing and sealing a solid component (especially a solid component having irregularities on the surface) using the packaging bag of the present invention.

[0255] Examples

[0256] Hereinafter, examples and comparative examples are shown to more specifically illustrate the features of the present invention. However, the scope of the present invention is not limited to the examples.

[0257] 1. Regarding the raw materials used

[0258] The raw materials used in each example and comparative example are as follows.

[0259] (1) Thermoplastic resin for forming the plastic substrate (I)

[0260] · PA6: Nylon 6 resin (manufactured by Unitika Ltd., "A1030BRF", relative viscosity 3.0)

[0261] (2) Metal compound for forming the plastic substrate (I)

[0262] MgO: magnesium oxide ("PUREMAG FNM-G" manufactured by Tateho Chemical Industries, average particle size 0.54 μm)

[0263] (3) Master sheet containing a metal compound for forming a plastic substrate (I)

[0264] Mother sheet 1: 95 parts by mass of the above-mentioned PA6 and 5 parts by mass of MgO were kneaded and prepared.

[0265] Mother sheet 2: 75 parts by mass of the above-mentioned PA6 and 25 parts by mass of MgO were kneaded and prepared.

[0266] (4) Polycarboxylic acid component of the coating liquid for forming the gas barrier layer (II)

[0267] EMA aqueous solution:

[0268] EMA (weight average molecular weight 60,000) and sodium hydroxide were added to water, heated to dissolve, and then cooled to room temperature to prepare an EMA aqueous solution in which 10 mol % of carboxyl groups of EMA were neutralized with sodium hydroxide and the solid content was 15 mass %.

[0269] PVA aqueous solution:

[0270] Polyvinyl alcohol (5-98 manufactured by Kuraray Co., Ltd., saponification degree 98 to 99%, average polymerization degree about 500) was added to water, heated to dissolve, and then cooled to room temperature to prepare a polyvinyl alcohol (PVA) aqueous solution having a solid content of 15% by mass.

[0271] (5) Mineral oil

[0272] ・"AGITAN282" manufactured by MUNZING CHEMIE GmbH (referred to as "mineral oil A" in the table)

[0273] ・"SN DEFOAMER 154S" manufactured by San Nopco (represented as "mineral oil B" in the table)

[0274] · EVONIK "AIRASE 4655" (represented as "vegetable oil" in the table)

[0275] (6) Surfactants

[0276] · Acetylene glycol nonionic surfactant: "OLFINE E1004" manufactured by Nissin Chemical Industry Co., Ltd.

[0277] Anionic surfactant: "Nopco 1338" manufactured by San Nopco

[0278] 2. Examples and Comparative Examples

[0279] [Example 1]

[0280] Nylon 6 resin and mother sheet 1 were mixed in such a way that the content of magnesium oxide was 0.5% by mass. The mixture was put into an extruder and melted in a barrel at 270°C. The melt was extruded from a T-die hole into a sheet, and it was made to fit tightly with a rotating drum cooled to 10°C and quenched, thereby obtaining an unstretched plastic substrate (I) film with a thickness of 150 μm formed by a metal-containing layer (M). The obtained unstretched film was sent to a warm water tank at 50°C and subjected to a water absorption treatment for 2 minutes (water absorption rate 5%).

[0281] Next, a mixed solution a was prepared by mixing a PVA aqueous solution and an EMA aqueous solution so that the mass ratio (solid content) of PVA to EMA was 30 / 70.

[0282] Here, a pre-dispersion liquid is first prepared. 0.15% of the total weight of the prepared mixed liquid a is extracted (extraction rate). In this case, the extracted mixed liquid is referred to as mixed liquid a2, and the remaining mixed liquid is referred to as mixed liquid a1.

[0283] Mineral oil (A) was mixed into the mixed liquid a2, and the acetylene glycol nonionic surfactant was added into the mixed liquid a2 in such a manner that the mass ratio of mineral oil / acetylene glycol nonionic surfactant was 60 / 40. The amount of the mineral oil and the acetylene glycol nonionic surfactant added into the mixed liquid a2 was 0.113 parts by mass of the mineral oil (A) and 0.073 parts by mass of the acetylene glycol nonionic surfactant relative to 100 parts by mass of the total mass (solid content) of PVA and EMA.

[0284] Next, the mixed solution a2 to which the mineral oil (A) and the acetylene glycol-based nonionic surfactant were added was dispersed at 5000 rpm for 30 minutes using a high-speed rotating homomixer to prepare a preliminary dispersion.

[0285] Then, the pre-dispersion liquid was added to the mixed liquid a1 to obtain a raw material liquid as an aqueous dispersion liquid. Next, the raw material liquid was passed through a commercially available filter ("CLEAL BM FILTER, BM-03", manufactured by JNC FILTER Co., Ltd., with a filtration accuracy of 3 μm) to prepare a coating liquid for forming a gas barrier layer (II) having a solid content of 10% by mass. The median particle size of the droplets of the obtained coating liquid was 0.45 μm.

[0286] The contents of mineral oil and acetylene glycol nonionic surfactant in the raw material solution (the coating solution) are 0.017 parts by mass of mineral oil and 0.011 parts by mass of acetylene glycol nonionic surfactant, respectively, relative to 100 parts by mass of the total mass (solid content) of PVA and EMA.

[0287] The coating liquid is applied to one side of an unstretched film subjected to water absorption treatment, and then dried. The ends of the unstretched film coated with the coating liquid and dried are held in the clamps of a tenter-type simultaneous biaxial stretching machine, and stretched to 3.3 times in the MD and TD directions at 180°C. Then, the relaxation rate in TD is set to 5%, and a heat treatment is performed at 210°C for 4 seconds, and then slowly cooled to room temperature to obtain a gas barrier laminate having a gas barrier layer (II) with a thickness of 0.3 μm stacked on a plastic substrate (I) with a thickness of 15 μm formed by a single layer of a metal-containing layer (M).

[0288] [Examples 2 to 3, 14]

[0289] A gas barrier layered product was obtained in the same manner as in Example 1 except that the addition amounts and ratios of the mineral oil (A) and the acetylene glycol nonionic surfactant were set to the amounts shown in Table 1.

[0290] [Example 4]

[0291] Nylon 6 resin and mother sheet 2 were put into extruder A in such a way that the magnesium oxide content was 10% by mass, and melted in a barrel at 270°C. On the other hand, nylon 6 resin was put into extruder B and melted in a barrel at 270°C. The two resins melted in extruder A and extruder B were overlapped in the die head, and a sheet consisting of two layers of metal-containing layer (M) / resin layer (R) was extruded from a T die, and it was closely attached to a rotating drum cooled to 10°C and quenched, thereby obtaining an unstretched plastic substrate (I) film with a thickness of 150 μm and (M) / (R)=30 / 120 μm. The above-mentioned unstretched plastic substrate (I) film was set as described in Table 1, and the same operation as in Example 1 was performed to obtain a gas barrier laminate.

[0292] [Examples 5 and 6]

[0293] A gas barrier layered product was obtained in the same manner as in Example 1 except that a film having a thickness of the unstretched plastic substrate (I) composed of the metal-containing layer (M) described in Table 1 was obtained.

[0294] [Examples 7, 8, 9]

[0295] A gas barrier layered product was obtained in the same manner as in Example 1 except that the magnesium oxide content of the metal-containing layer (M) was set as described in Table 1.

[0296] [Examples 10 and 11]

[0297] A gas barrier layered product was obtained in the same manner as in Example 1 except that the thickness of the gas barrier layer (II) was set to the thickness described in Table 1.

[0298] [Examples 12 and 13]

[0299] A gas barrier laminate was obtained in the same manner as in Example 1 except that the neutralization degree of the polyvalent carboxylic acid was set to the degree described in Table 1 in the coating liquid composition for forming the gas barrier layer (II).

[0300] [Example 15]

[0301] As shown in Table 1, a gas barrier laminate was obtained in the same manner as in Example 1 except that “SN DEFOAMER 154S” manufactured by San Nopco was used as the mineral oil (B).

[0302] [Comparative Example 1]

[0303] As shown in Table 2, a gas barrier layered product was obtained in the same manner as in Example 1 except that pure water was used instead of the mixed solution a2 when preparing the preliminary dispersion.

[0304] [Comparative Example 2]

[0305] As shown in Table 2, a gas barrier laminate was obtained in the same manner as in Example 1 except that a commercially available anionic surfactant "Nopco 1338" was used instead of the acetylene glycol nonionic surfactant "OLFINE E1004".

[0306] [Comparative Examples 3 and 4]

[0307] A gas barrier layered product was obtained in the same manner as in Example 1 except that the added amounts and ratios of the mineral oil and the acetylene glycol nonionic surfactant were changed to those shown in Table 2.

[0308] [Comparative Example 5]

[0309] As shown in Table 2, a gas barrier layered product was obtained in the same manner as in Comparative Example 1 except that the acetylene glycol-based surfactant was not added.

[0310] [Comparative Example 6]

[0311] As shown in Table 2, a gas barrier layered product was obtained in the same manner as in Example 1 except that the mineral oil was directly added to the mixed liquid a without pre-dispersion.

[0312] [Comparative Example 7]

[0313] A gas barrier layered product was obtained in the same manner as in Example 4 except that the magnesium oxide content of the metal-containing layer (M) was set to be as shown in Table 2 and pure water was used instead of the mixed solution a2 when preparing the preliminary dispersion.

[0314] [Comparative Example 8]

[0315] A gas barrier laminate was obtained in the same manner as in Comparative Example 5 except that a film having the thickness of the unstretched plastic substrate (I) formed by the thickness of the metal-containing layer (M) described in Table 2 was obtained.

[0316] [Comparative Examples 9 and 10]

[0317] A gas barrier layered product was obtained in the same manner as in Comparative Example 5 except that the thickness of the gas barrier layer (II) was set to the thickness described in Table 2.

[0318] [Comparative Examples 11 and 12]

[0319] Except having set the magnesium oxide content of the metal-containing layer (M) so as to be described in Table 2, it carried out similarly to Comparative Example 5, and obtained the gas barrier layered product.

[0320] [Comparative Example 13]

[0321] As shown in Table 2, a gas barrier layered product was obtained in the same manner as in Comparative Example 5 except that the neutralization of the polyvalent carboxylic acid was not performed.

[0322] [Comparative Example 14]

[0323] A gas barrier laminate was obtained in the same manner as in Comparative Example 5 except that the neutralization degree of the polyvalent carboxylic acid was set to the degree described in Table 2 in the coating liquid composition for forming the gas barrier layer (II).

[0324] [Comparative Example 15]

[0325] As shown in Table 2, a gas barrier laminate was obtained in the same manner as in Example 1 except that the vegetable oil "AIRASE 4655" manufactured by EVONIK Corporation was used instead of the mineral oil.

[0326] [Comparative Example 16]

[0327] As shown in Table 2, a gas barrier laminate was obtained in the same manner as in Example 1 except that mineral oil was not added to the coating liquid for forming the gas barrier layer (II).

[0328] [Comparative Examples 17 and 18]

[0329] A gas barrier layered product was obtained in the same manner as in Example 1 except that the addition amounts and ratios of the mineral oil and the acetylene glycol nonionic surfactant were set as shown in Table 2.

[0330] [Comparative Example 19]

[0331] A gas barrier layered product was obtained in the same manner as in Comparative Example 5, except that the magnesium oxide content of the metal-containing layer (M), the thickness of the gas barrier layer (II), and the thickness of the unstretched plastic substrate (I) formed by the thickness of the metal-containing layer (M) were obtained as shown in Table 2.

[0332] [Test Example 1]

[0333] The gas barrier layered products obtained in each of the Examples and Comparative Examples were evaluated for the following properties. The results are shown in Tables 3 and 4.

[0334] (1) Thickness of each layer

[0335] The obtained gas barrier layered product was placed in an environment of temperature 23°C and humidity 50% RH for more than 2 hours, and then the film cross section was observed using a scanning electron microscope (SEM) (magnification 40,000 times) to measure the thickness of each layer. The thickness was measured at any three locations using the above method, and the average value was shown.

[0336] (2) Median particle size of mineral oil droplets in the coating liquid for forming the gas barrier layer (II)

[0337] The coating liquid for forming the gas barrier layer (II) immediately before being applied to the unstretched film was used as a measurement sample and measured using a laser diffraction particle size distribution analyzer (SALD-2300) manufactured by Shimadzu Corporation. The median particle size (D50) was taken as the average particle size.

[0338] (3) Elastic modulus and hardness of gas barrier layer (II) (nanoindenter)

[0339] The elastic modulus and hardness of the gas barrier layer (II) are measured using a nanoindenter (Triboindenter manufactured by Hysitron Inc.). At this time, as an indenter, a Berkovich indenter (triangular pyramid indenter) is used (3-sided pyramid structure, the inner angle of the indenter is 142.35°, the angle between the center line and the surface is 65.35°, and the aspect ratio of the indenter is 1:8). Specifically, the elastic modulus and hardness of the gas barrier layer (II) are measured as follows: the gas barrier laminate (with the gas barrier layer (II) as the upper surface) is fixed on a glass plate, and the above-mentioned nanoindenter is used to measure the state in which the indenter is only pressed into the gas barrier layer (II) by 10 nm under an environment of 25°C. The measurement method uses a single indentation measurement method. The elastic modulus and hardness are measured at any 10 locations by the above method, and the average value is shown.

[0340] (4) Oxygen permeability before elongation

[0341] After the gas barrier laminates obtained in each example and comparative example were subjected to a 120°C × 30-minute steaming treatment, the oxygen permeability was measured using an oxygen permeability measuring device "OX-TRAN 2 / 22L" manufactured by MOCON (sample size 10.8 cm × 10.8 cm) under (a) a temperature of 20°C and a humidity of 90% RH and (b) a temperature of 40°C and a humidity of 90% RH. The unit is ml / (m 2 ·day·MPa).

[0342] (5) Oxygen permeability after elongation

[0343] The gas barrier laminate obtained in each example and comparative example was subjected to a steaming treatment at 120°C for 30 minutes, and then stretched by 7% in both MD and TD at 35°C and 50%RH using a biaxial stretching device "Karo IV" manufactured by Brucker. The gas barrier laminate was then subjected to an oxygen permeability measurement device (OX-TRAN 2 / 22L) manufactured by Mocon (sample size 10.8 cm × 10.8 cm) to measure the oxygen permeability in (a) 20°C and 90%RH and (b) 40°C and 90%RH environments. The unit is ml / (m 2 ·day·MPa).

[0344] (6) Evaluation of oxygen barrier properties after bending

[0345] On the gas barrier layer (II) of the gas barrier laminate obtained in each example and comparative example, a two-component curable polyurethane adhesive (DIC Graphics Co., Ltd., LX-500 / KR-90) was applied with a coating thickness of 4 μm (when dry) by gravure roll coating, and a 50 μm thick unstretched polypropylene film (Mitsui Chemicals Tohcello Co., Ltd., CPP RXC-22) was dry-laminated as a sealant layer, and allowed to stand at 20°C and 40°C for 72 hours, respectively. In this way, a gas barrier laminate laminate film (test sample) was produced.

[0346] The obtained laminated film was treated 10 times with a Gelbo Flex tester (manufactured by TESTERSANGYO CO., LTD.) under an environment of a temperature of 23° C. and a humidity of 50% RH.

[0347] (6-1) Oxygen permeability

[0348] The laminated film treated 10 times with the Gelbo Flex tester was subjected to a 120°C × 30-minute steaming treatment, and then the oxygen permeability was measured using an oxygen permeability measuring device (OX-TRAN 2 / 22L) manufactured by MOCON (sample size 10.8 cm × 10.8 cm) under (a) a temperature of 20°C and a humidity of 90% RH and (b) a temperature of 40°C and a humidity of 90% RH. The unit is ml / (m 2 ·day·MPa).

[0349] (6-2) Gas barrier layer evaluation based on image processing

[0350] A three-side sealed bag with the dimensions of 100 mm in width and 150 mm in height was prepared using a laminated film treated 10 times with the above-mentioned Gelbo Flex tester, with the sealing layer being the inner surface. The bag was filled with the following adjustment liquid, and the remaining side was sealed by heat sealing. The sealed three-side sealed bag was subjected to a retort treatment at 120°C for 30 minutes, and a photo of the three-side sealed bag was taken on a white paper. The blue portion of the three-side sealed bag after treatment indicates the portion where oxygen permeates due to a poor gas barrier layer (II).

[0351] The captured photo was converted into black and white (the scale setting of the chroma was changed to 0.0) using the image processing software "GIMP 2.10", and the area ratio of the white and black parts was calculated. The threshold for evaluating the area ratio was set to 155 in the grayscale of 0 to 255. The gas barrier layer after bending was evaluated according to the following scoring criteria. The area ratio of the blue part (oxygen permeable part) based on image processing was set to "0" when it was less than 0.1%, "△" when it was more than 0.1% and less than 0.3%, and "×" when it exceeded 0.3%.

[0352] The adjustment solution was prepared by adding 0.5 g of methylene blue, 1.0 g of thioglycolic acid, and 1000 ml of ion-exchanged water into a container and stirring the mixture.

[0353] (7) Evaluation of aroma retention

[0354] Using the laminated film obtained in the same manner as in the above "(6) Evaluation of oxygen barrier properties after bending", a three-side sealed bag with the dimensions of 100 mm in height and 100 mm in width was prepared. 20 mL of a 3 wt % aqueous solution of ethanol as a flavor retainer was filled into the bag, and the remaining side was heat-sealed to seal it. The three-side sealed bag filled with the 3 wt % aqueous solution of ethanol was placed in an aluminum foil bag for vacuum packaging, and 100 cc of air captured by a syringe was injected into the vacuum-packaged aluminum bag and resealed. After being stored for one month at a temperature of 40°C and a relative humidity of 90% RH, the concentration of ethanol leaking into the aluminum foil bag was measured using a Kitagawa gas sampler (manufactured by Komyo Rikagaku Kogyo Co., Ltd.). The flavor retainer was evaluated according to the following scoring criteria.

[0355] When the ethanol concentration was less than 0.05%, it was recorded as "0", when it was 0.05% or more and 0.1% or less, it was recorded as "△", and when it exceeded 0.1%, it was recorded as "×".

[0356]

Table 1

[0357]

[0358]

Table 2

[0359]

[0360]

Table 3

[0361]

[0362]

Table 4

[0363]

[0364] According to the results in Tables 3 to 4, Examples 1 to 15 are gas barrier laminates produced by using a coating liquid in which a mineral oil and an acetylene glycol-based nonionic surfactant are blended at a certain ratio and a pre-dispersion liquid in which the mineral oil is sufficiently dispersed. Therefore, the elastic modulus of the surface of the gas barrier layer (II) after the retort treatment satisfies a specific range, and the excellent gas barrier properties can be exhibited even in a high temperature and high humidity environment after vacuum packaging, and the excellent bending resistance, aroma retention, etc. are exhibited.

[0365] Regarding the gas barrier laminates of Comparative Examples 1 and 7, pure water was used instead of the mixed solution a2 when preparing the pre-dispersion solution. Therefore, the dispersibility of the mineral oil and the acetylene glycol-based nonionic surfactant could not be fully obtained, and the elastic modulus of the surface of the gas barrier layer (II) after the retort treatment could not meet the specific range. As a result, the gas barrier properties in a high temperature and high humidity environment after vacuum packaging could not be obtained.

[0366] Since the gas barrier laminate of Comparative Example 2 contains an anionic surfactant instead of an acetylene glycol-based nonionic surfactant, the elastic modulus of the surface of the gas barrier layer (II) after retorting cannot meet the specific range, and gas barrier properties cannot be obtained in a high temperature and high humidity environment after vacuum packaging.

[0367] Since the gas barrier laminates of Comparative Examples 5 to 6, 8 to 14, and 19 did not contain an acetylene glycol-based nonionic surfactant, the elastic modulus of the surface of the gas barrier layer (II) after retorting treatment did not satisfy the specific range, and gas barrier properties in a high-temperature and high-humidity environment after vacuum packaging could not be obtained.

[0368] Since the gas barrier laminates of Comparative Examples 15 and 16 did not contain mineral oil, the elastic modulus of the surface of the gas barrier layer (II) after retorting did not meet the specific range, and gas barrier properties in a high temperature and high humidity environment after vacuum packaging could not be obtained.

[0369] On the other hand, Comparative Examples 3 to 4 and 17 to 18 are gas barrier laminates produced using a coating liquid in which the mineral oil and the acetylene glycol-based nonionic surfactant are not blended at a certain ratio. Therefore, the elastic modulus of the surface of the gas barrier layer (II) after the retort treatment cannot satisfy the specific range, and the gas barrier properties in a high-temperature and high-humidity environment after vacuum packaging cannot be obtained.

Claims

1. A gas barrier laminate, characterized in that: The gas barrier layer comprises a plastic substrate (I) and a gas barrier layer (II) laminated on the plastic substrate, wherein the total thickness of the gas barrier layer is 100 μm or less. (1) The plastic substrate (I) comprises a metal-containing layer, wherein the metal-containing layer comprises at least one of a metal and a metal compound and a resin component, (2) The total content of the metal and the metal compound in the metal-containing layer is 0.1% by mass to 20% by mass, (3) The gas barrier layer (II) contains a polycarboxylic acid, (4) the metal-containing layer and the gas barrier layer are laminated in direct contact with each other, (5) The complex elastic modulus of the surface of the gas barrier layer (II) after the laminate was subjected to a retort treatment at 120° C. for 30 minutes, measured by a nanoindentation method, was 9.0 GPa to 12.5 GPa.

2. The gas barrier layered product according to claim 1, wherein The hardness of the surface of the gas barrier layer (II) after the laminate was subjected to a retort treatment at 120° C. for 30 minutes was measured by a nanoindentation method and was 0.7 GPa to 1.3 GPa.

3. The gas barrier layered product according to claim 1, wherein The laminate was subjected to a steaming treatment at 120°C for 30 minutes, and then stretched by 7% in both the MD and TD directions at a rate of 1.5% / s under a temperature of 35°C and a humidity of 50% RH. The oxygen permeability of the laminate under a temperature of 40°C and a humidity of 90% RH was 100 ml / (m 2 ·day·MPa) or less.

4. The gas barrier layered product according to claim 1, wherein The plastic substrate (I) consists of a multilayer film comprising a metal-containing layer.

5. The gas barrier layered product according to claim 1, wherein The gas barrier layer (II) further contains a polyol.

6. The gas barrier layered product according to claim 1, wherein The thickness of the gas barrier layer (II) is 0.05 μm to 5.00 μm, and the thickness of the plastic substrate (I) is 5 μm to 99.95 μm.

7. The gas barrier layered product according to claim 1, wherein The polycarboxylic acid includes at least one of polyacrylic acid, acrylic acid-maleic acid copolymer, and olefin-maleic acid copolymer.

8. The gas barrier layered product according to claim 1, wherein The resin component contained in the metal-containing layer includes one or more thermoplastic resins, and the content of the resin component in the metal-containing layer is 99.9% by mass to 80% by mass.

9. The gas barrier layered product according to claim 1, wherein The plastic substrate (I) is composed of one or more metal-containing layers and one or more other resin-containing layers, and the ratio of the total thickness (Mt) of the metal-containing layers (M) to the total thickness (Rt) of the other resin-containing layers (R), i.e., (Rt) / (Mt), is 1 / 10 to 10 / 1.

10. The gas barrier layered product according to claim 1, wherein The metal compound is at least one of lithium carbonate, sodium bicarbonate, magnesium oxide, magnesium carbonate, magnesium hydroxide, magnesium acetate, calcium oxide, calcium carbonate, calcium hydroxide, calcium chloride, calcium phosphate, calcium sulfate, calcium acetate, zinc acetate, zinc oxide and zinc carbonate.

11. The gas barrier layered product according to claim 1, wherein The gas barrier layer (II) comprises an olefin-maleic acid copolymer, and the content of maleic acid units in the olefin-maleic acid copolymer is 5 mol % or more.

12. The gas barrier layered product according to claim 1, wherein The metal and the metal compound are in the form of powder, and the average particle size is 0.005 μm to 5.0 μm. 13 . A packaging bag comprising the gas barrier layered product according to claim 1 .

14. A vacuum-packed product, wherein: In the packaging bag according to claim 13, at least a solid component is contained and sealed.

15. A method for producing a gas barrier layered product, characterized in that: A method for producing a gas barrier layered product, the method comprising: (1) preparing a raw material solution, wherein the raw material solution comprises a polycarboxylic acid, a mineral oil and an acetylene glycol-based nonionic surfactant, wherein the mass ratio of the mineral oil to the acetylene glycol-based nonionic surfactant is 80 / 20 to 40 / 60; and (2) A step of applying the raw material liquid as a coating liquid for forming a gas barrier layer (II) onto at least a surface of the metal-containing layer of a plastic substrate (I) comprising a metal-containing layer containing at least one of a metal and a metal compound and a resin component.

16. The manufacturing method according to claim 15, wherein: Before applying the raw material liquid to the plastic substrate (I), the method further includes preparing a coating liquid for forming a gas barrier layer (II) by passing the raw material liquid through a filter having a filtration accuracy of 1.0 μm to 10.0 μm.

17. The manufacturing method according to claim 16, wherein: The median particle size of the coating liquid for forming the gas barrier layer (II) after passing through the filter is 0.1 μm to 0.6 μm.

18. The method for producing a gas barrier layered product according to claim 15, wherein: After applying the raw material liquid to the plastic substrate (I), the method further includes subjecting the laminate coated with the raw material liquid to simultaneous biaxial stretching or sequential biaxial stretching.

Citation Information

Patent Citations

  • Sheet for draw forming, its manufacturing method and gas barrier object by draw forming

    JP2007276421A

  • Gas barrier laminate

    JP2019151025A

  • Laminate

    JP2015134465A

  • Gas barrier laminate

    JP2015150843A

  • Gas barrier laminate

    JP2017185652A